12beta-Hydroxylation of Digitoxin by Digitalis lanata Cells. Production of Deacetyllanatoside C in a 20-L Airlift Bioreactor. - Kreis, Wolfgang; Zhu, Weihua; Reinhard, Ernst (Biotechnology Letters, 1989)
UnivIS-Import:2015-03-05:Pub.1989.nat.dbio.LPB.12beta

12beta-Hydroxylation of Digitoxin by Suspension-Cultured Digitalis lanata Cells. Production of Deacetyllanatoside C Using a Two-Stage Culture Method - Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1988)
UnivIS-Import:2015-03-05:Pub.1988.nat.dbio.LPB.12beta

12beta-Hydroxylation of digitoxin by suspension-cultures Digitalis lanata cells: Production of digoxin in 20-litre and 300-litre air-lift bioreactors - Kreis, Wolfgang; Reinhard, Ernst (Journal of Biotechnology, 1992)
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.12beta

21-Hydroxypregnane 21-O-malonylation, a crucial step in cardenolide biosynthesis, can be achieved by substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases from Arabidopsis thaliana and homolog proteins from Digitalis lanata - Tropper, Marina; Höhn, Stephanie; Wolf, Laura-Sophie; Fritsch, Julia; Kastner-Detter, Nina; Rieck, Christoph; Munkert, Jennifer; Meitinger, Nadine; Lanig, Harald; Kreis, Wolfgang (Phytochemistry, 2021)
Three putative 21-hydroxypregnane 21-O-malonyltransferases (21MaT) from Digitalis lanata were partially purified.Two of them were supposed to be BAHD-type enzymes. We were unable to purify them in quantities necessary for reliable sequencing. We identified two genes in A. thaliana coding for substrate-promiscuous BAHDtype phenolic glucoside malonyltransferases (AtPMaT1, AtPMaT2) and docked various 21-hydroxypregnanes into the substrate-binding site of a homology model built on the BAHD template 2XR7 (NtMaT1 from N. tabacum). Recombinant forms of Atpmat1 and Atpmat2 were expressed in E. coli and the recombinant enzymes characterized with regard to their substrate preferences. They were shown to malonylate various 21-hydroxypregnanes. The Atpmat1 sequence was used to identify candidate genes in Digitalis lanata (Dlmat1 to Dlmat4). Dlmat1 and Dlmat2 were also expressed in E. coli and shown to possess 21-hydroxypregnane 21-O-malonyltransferase activity.<br
Keywords: Digitalis lanata; Plantaginaceae; Foxglove; Protein purification; Protein modeling; Gene expression analysis; Cardenolides; BAHD; Pregnane 21-O-malonyltransferase

3alpha-Hydroxysteroid-5beta-oxidoreductase in Tissue Cultures of Digitalis lanata. - Stuhlemmer, Ursel; Haussmann, Werner; Milek, Frank; Kreis, Wolfgang; Reinhard, Ernst (Zeitschrift für Naturforschung Section C - A Journal of Biosciences, 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.3alpha

Acetyl Coenzyme A:Digitoxin 15' -O-Acetyltransferase from Digitalis Plants and Suspension Cultures - Sutor, Renate; Kreis, Wolfgang; Hoelz, Hubert; Reinhard, Ernst (Phytochemistry, 1993)
The enzymatic acetylation of cardenolides was investigated. Suspension cultures of Digitalis grandiflora converted digitoxin to acetylated cardenolides such as α-acetyldigitoxin and lanatoside A. Protein preparations from the same source catalysed the transfer of an acetyl group from acetyl coenzyme A to the 15′-O-position of digitoxin or digoxin. The enzyme involved, acetyl coenzyme A: digitoxin 15′-O-acetyltransferase, was characterized and detected in protein extracts from other tissues, namely the leaves of D. grandiflora, as well as the leaves, callus and suspended cells of D. lanata. Compartmentalization studies with isolated protoplasts and vacuoles revealed that the digitoxin acetyltransferase is a soluble cytosolic enzyme. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.acetyl
Keywords: acetylation; cardenolides; cardiac glycosides; compartmentalization; D. lanata; Digitalis grandiflora; Scrophulariaceae; vacuoles.

A Flavone-Glucoside-Cleaving beta-Glucosidase from Chamomilla recutita. - Maier, Reinhard; Kreis, Wolfgang; Carle, Reinhold; Reinhard, Ernst (Planta Medica, 1991)
UnivIS-Import:2015-03-05:Pub.1991.nat.dbio.LPB.aflavo

A new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) affects G2/M cell cycle arrest and miRNA expression profiles and enhances proapoptotic survivin-2B expression in renal cell carcinoma cell lines - Nolte, Elke; Wach, Sven; Silva, Izabella Thais; Lukat, Sabine; Ekici, Arif Bülent; Munkert, Jennifer; Müller-Uri, Frieder; Kreis, Wolfgang; Simões, Cláudia M. O.; Vera González, Julio; Wullich, Bernd; Taubert, Helge; et al. (Oncotarget, 2017)
EVALuna2:9377
Keywords: Cardiac glycoside analog; Cell cycle; 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin; Human renal cell carcinoma cells; MiRNA

A non-invasive method for the routine-estimation of fresh weight of cells grown in batch suspension cultures. - Blom, T.J.M.; Kreis, Wolfgang; van Iren, F.; Libbenga, K.R. (Plant Cell Reports, 1992)
A simple apparatus was designed to allow sedimentation of plant cells grown in batch suspensions in Erlenmeyer flasks. After sedimentation the height of the cell mass along the glass wall was measured with a ruler fixed in the apparatus. The cell volume after sedimentation, calculated from this height, appeared highly correlated with the fresh weight of cells. This result was found with eight cell lines in two Laboratories. The method proved to be very suitable to allow routinely measurement of FW without the destruction of cells, from many samples, in a short time, during each phase of the growth cycle. © 1992 Springer-Verlag.
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.anonin

Antiherpes activity of glucoevatromonoside, a cardenolide isolated from a Brazilian cultivar of Digitalis lanata. - Bertol, Jessica Wildgrube; Rigotto, Caroline; Maia de Pádua, Rodrigo; Kreis, Wolfgang; Barardi, Célia Regina Monte; Braga, Fernão C.; Simões, Cláudia M. O. (Antiviral Research, 2011)
Cardiac glycosides, known ligands of the sodium pump, are widely used in the treatment of heart failure, such as digoxin and digitoxin. Besides this important activity, other biological activities, such as the antiviral activity, have been described for this group. HSV are responsible for many infections of oral, ocular and genital regions. Treatment with nucleoside analogs such as acyclovir is effective in most cases; however drug-resistance may arise due to prolonged treatment mainly in immunocompromised individuals. In this study, an antiherpes screening was performed with 65 cardenolide derivatives obtained from different sources, and one natural cardenolide, glucoevatromonoside, inhibited HSV-1 and HSV-2 replication at very low concentrations. This cardenolide showed viral inhibitory effects if added up to 12h p.i. and these effects appear to take place by the inhibition of viral proteins synthesis (ICP27, U L42, gB, gD), the blockage of virus release and the reduction of viral cell-to-cell spread. This compound also showed synergistic antiviral effects with acyclovir and anti-Na +K +ATPase activity, suggesting that cellular electrochemical gradient alterations might be involved in the mechanism of viral inhibition. These results suggest that cardenolides might be promising for future antiviral drug design. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.nat.dbio.LPB.antihe
Keywords: Antiherpes; Cardiac glycoside; Glucoevatromonoside; HSV-1

Arzneistoffe aus pflanzlichen Zell- und Gewebekulturen. Möglichkeiten und Grenzen - Kreis, Wolfgang (Deutsche Apotheker Zeitung, 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.herste

A simple chemical method for synthesizing malonyl hemiesters of 21-hydroxy-pregnanes, potential intermediates in cardenolide biosynthesis. - Maia de Pádua, Rodrigo; Waibel, Reiner; Kuate, Serge Philibert; Schebitz, Pia; Hahn, Stefanie; Gmeiner, Peter; Kreis, Wolfgang (Steroids, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.asimpl

Avaliação quantitativa de cardenolídeos no cultivar experimental de Digitalis lanata do maciço do itatiaia e perspectivas de seu emprego industrial - Braga, Fernão Castro; Kreis, Wolfgang; Récio, Rubens Almeida; De Oliveira, Alaíde Braga (Quimica Nova, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.avalia

A young root-specific gene (ArMY2) from horseradish encoding a MYR II myrosinase with kinetic perference for the root-specific glucosinolate gluconasturtiin - Loebers, Andreas; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2014)

BAHD-like malonyltransferase genes from Digitalis lanata and Arabidopsis thaliana and their putative role in cardenolide biosynthesis - Tropper, Marina; Höhn, Stephanie; Munkert, Jennifer; Kreis, Wolfgang (PLANTA MEDICA, 2019)
CRIS-Team WoS Importer:2020-01-10

Biochemistry of sterols, cardiac glycosides, brassinosteroids, phytoecdysteroids and steroid saponins - Kreis, Wolfgang; Müller-Uri, Frieder (Biochemistry of Plant Secondary Metabolism. Annual Review Plant, 2010)
UnivIS-Import:2015-04-20:Pub.2010.nat.dbio.LPB.bioche
Keywords: biosynthesis; cardiac glycosides; ecdysteroids; metabolic pathways; phylogeny; pregnanes; saponins; secondary metabolites; withanolides

Biochemistry of terpenoids: monoterpenes, sesquiterpenes, diterpenes, sterols, cardiac glycosides and steroid saponins. - Gershenzon, Jonathan; Kreis, Wolfgang (Biochemistry of Plant Secondary Metabolism, 1999)
UnivIS-Import:2015-04-20:Pub.1999.nat.dbio.LPB.bioche

Biossíntese de metabólitos primários e secundários - Kreis, Wolfgang; Munkert, Jennifer; De Padua, Rodrigo Maia (Farmacognosia do Produto Natural ao Medicamento, 2017)

Biosynthetic approach to combine the first steps of cardenolide formation in Saccharomyces cerevisiae - Rieck, Christoph; Geiger, Daniel; Munkert, Jennifer; Messerschmidt, Katrin; Petersen, Jan; Strasser, Juliane; Meitinger, Nadine; Kreis, Wolfgang (MicrobiologyOpen, 2019)
A yeast expression plasmid was constructed containing a cardenolide biosynthetic module, referred to as CARD II, using the AssemblX toolkit, which enables the assembly of large DNA constructs. The genes cloned into the vector were (a) a Δ5-3β-hydroxysteroid dehydrogenase gene from Digitalis lanata, (b) a steroid Δ5-isomerase gene from Comamonas testosteronii, (c) a mutated steroid-5β-reductase gene from Arabidopsis thaliana, and (d) a steroid 21-hydroxylase gene from Mus musculus. A second plasmid bearing an ADR/ADX fusion gene from Bos taurus was also constructed. A Saccharomyces cerevisiae strain bearing these two plasmids was generated. This strain, termed “CARD II yeast”, was capable of producing 5β-pregnane-3β,21-diol-20-one, a central intermediate in 5β-cardenolide biosynthesis, starting from pregnenolone which was added to the culture medium. Using this approach, five consecutive steps in cardenolide biosynthesis were realized in baker's yeast.
CRIS-Team Scopus Importer:2019-08-30
Keywords: baker's yeast; biosynthesis; cardenolides; pathway engineering; steroids

Biotechnologie der Arzneistoffe. - Kreis, Wolfgang; Baron, Dieter K.; Stoll, Günther (Deutscher Apotheker Verlag, 2001)
UnivIS-Import:2015-04-02:Pub.2001.nat.dbio.LPB.biotec

Biotechnologie für Pharmazeuten - Kreis, Wolfgang; Stoll, Günther (Deutsche Apotheker Zeitung, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.biotec_83

Biotechnologische Optimierung der Wirkstoffproduktion bei Arznei- und Gewürzpflanzen - Kreis, Wolfgang (Zeitschrift für Arznei- & Gewürzpflanzen, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.biotec

Biotransformation of 21-O-acetyl-deoxycorticosterone by cell suspension cultures of Digitalis lanata (strain W.1.4) - Maia de Pádua, Rodrigo; Meitinger, Nadine; de Souza Filho, José Dias; Waibel, Reiner; Gmeiner, Peter; Braga, Fernão C.; Kreis, Wolfgang (Steroids, 2012)
Cell cultures of Digitalis species are known to accept exogenous substrates for biotransformation reactions. We here report the biotransformation of 21-O-acetyl-deoxycorticosterone (1) by cell suspension cultures of Digitalis lanata strain W.1.4. Nine derivatives of 1 were obtained and their chemical structures determined by spectroscopic methods. 2β-Hydroxylation and C-21-glucosylation of the steroidal nucleus were described for the first time in suspension-cultured plant cells. Steroid 5α- and 5β-reduction products were also observed. Among the compounds isolated and structures elucidated were 2β,3β,21-trihydroxy-4-pregnen-20-one, 2β,3α,21-trihydroxy-4-pregnen-20-one and 3β,21-dihydroxy- 5α-pregnan-20-one-3β-O-β-glucoside. © 2012 Elsevier Inc. All rights reserved.

Buckwheat is a Source for the Herbal Drug Fagopyri herba: Rutin Content and Activity of Flavonoid-Degrading Enzymes during Plant Development. - Baumgertel, Andreas; Loebers, Andreas; Kreis, Wolfgang (The European Journal of Plant Science and Biotechnology, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dbio.LPB.buckwh

Burren - Rocks and Loughs. - Kreis, Wolfgang; Christmann, Alexander (Student und Praktikant, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.burren

Cardenolide aglycone formation in Digitalis - Kreis, Wolfgang; Müller-Uri, Frieder (Isoprenoid Synthesis in Plants and Microorganisms: New Concepts and Experimental Approaches, 2013)
UnivIS-Import:2015-04-20:Pub.2013.nat.dbio.LPB.carden

Cardenolide and glucosinolate accumulation in shoot cultures of Erysimum crepidifolium Rchb. - Horn, Elisa; Kemmler, Yvonne; Kreis, Wolfgang; Munkert, Jennifer (In Vitro Cellular & Developmental Biology-Plant, 2020)
Erysimum crepidifolium Rchb. is one of the few Brassicaceae species accumulating glucosinolates as well as cardenolides. This is possibly providing a selective advantage in evolution as both compounds are part of a chemical defense system. In order to study the biosynthesis of these compounds, a regeneration protocol for E. crepidifolium using in vitro shoot cultures derived from seeds has been developed. Murashige and Skoog (MS) culture medium supplemented with various combinations of cytokinins and auxins was used. MS medium containing NAA (naphthaleneacetic acid, 0.04 mg mL−1) and BAP (6-benzylaminopurine, 0.2·10−2 mg mL−1) proved to be optimal for root formation. Plantlets developed well on modified MS medium without the use of phytohormones. About 80% of the plantlets rooted in vitro developed into intact plants after transfer to the greenhouse. Cardenolides (1.75 mg g−1 dry weight (DW)) were detected in cultured shoots on solid DDV media while glucosinolates mainly accumulated in roots where 0.025 mg g−1 FW were detected in shoots cultured on the same medium (DDV). The expression of two progesterone 5β-reductase and three Δ5-3β-hydroxysteroid dehydrogenase genes were measured in shoot cultures since the encoded enzymes are supposed to be involved in cardenolide biosynthesis. E. crepidifolium shoot cultures propagated on solid media meet the necessary requirements, i.e., clonal homogeneity, product accumulation, and gene expression, for a suitable model to study cardenolide but not glucosinolate biosynthesi

Cardenolide Biosynthesis in Foxglove - Kreis, Wolfgang; Hensel, Andreas; Stuhlemmer, Ursel (Planta Medica, 1998)
The article reviews the state of knowledge on the biosynthesis of cardenolides in the genus Digitalis. It summarizes studies with labelled and unlabelled precursors leading to the formulation of the putative cardenolide pathway. Alternative pathways of cardenolide biosynthesis are discussed as well. Special emphasis is laid on enzymes involved in either pregnane metabolism or the modification of cardenolides. About 20 enzymes which are probably involved in cardenolide formation have been described 'downstream' of cholesterol, including various reductases, oxido-reductases, glycosyl transferases and glycosidases as well as acyl transferases, acyl esterases and P450 enzymes. Evidence is accumulating that cardenolides are not assembled on one straight conveyor belt but instead are formed via a complex multidimensional metabolic grid. For example 'fucose-type' cardenolides and 'digitoxosetype; cardenolides seem to form via different biosynthetic branches and the 'norcholanic acid pathway' identified recently seems to be operative only in the formation of fucose-type cardenolides.
UnivIS-Import:2015-03-05:Pub.1998.nat.dbio.LPB.carden
Keywords: Biosynthesis; Cardenolides; Cardiac glycosides; Digitalis; Enzymes; Feeding experiments; Glycosidase; Glycosyl transferase; Oxido-reductases; Scrophulariaceae; Secondary metabolism; Tracer studies

Cardenolide biosynthesis in light- and dark-grown Digitalis lanata shoot cultures - Eisenbeiß, Marina; Kreis, Wolfgang; Reinhard, Ernst (Plant Physiology and Biochemistry, 1999)
Shoot cultures of the cardenolide-producing species Digitalis lanata Ehrh. accumulated up to 0.6 μmol cardenolides per g dry mass when cultivated under continuous white light. After transfer to permanent dark, the cardenolide content of cultured shoots gradually decreased and reached non-detectable levels after 12 weeks. After transfer back to light conditions, cardenolides started to accumulate and reached the levels of light-grown controls after 4 weeks. Radiolabelled pregnenolone and progesterone were incorporated into cardenolides in both green light-grown and white dark-grown shoots. It was thus established that cardenolides are synthesised de novo in chloroplast-free tissues without apparent cardenolide accumulation, indicating that these compounds are efficiently turned over in the dark and that tissue differentiation, but not intact chloroplasts, is essential for cardenolide formation. The time course of two late anabolic enzymes of cardenolide metabolism, acetyl-CoA:digitoxin 15'-O-acetyltransferase (DAT, EC 2.3.1.-) and UDP-glucose:digitoxin 16'-glucosyltransferase (DGT, EC 2.4.1.-) was established during transfer of shoots from light to dark and vice versa. Only DAT was affected and was not measurable any more under dark conditions. The DGT may not be down-regulated because of its important, maybe even vital, role as an enzyme providing the vacuolar storage forms of cardenolides. Two catabolic cardenolide-specific enzymes, lanatoside 15'-O-acetylesterase (LAE, EC 3.1.1.6.) and cardenolide 16'-O-glucohydrolase I (CGH I, EC 3.2.1.21), were also investigated and it was demonstrated that CGH I is inactive in dark-grown shoots. These observations indicate that CGH I is not involved in cardenolide degradation in situ, but may instead play a role in cardenolide remetabolisation and activation after wounding or in developmental programs.
UnivIS-Import:2015-03-05:Pub.1999.nat.dbio.LPB.carden_99
Keywords: Biosynthesis; Cardiac glycosides; Digitalis lanata; Enzymes; Pregnenolone; Progesterone; Shoot cultures

Cardenolide estimation in callus-mediated regenerants of Digitalis lamarckii Ivanina (dwarf foxglove) - Yücesan, Buhara; Müller-Uri, Frieder; Kreis, Wolfgang; Gürel, Ekrem (In Vitro Cellular & Developmental Biology-Plant, 2013)

Cardenolide formation and activity of pregnane-modifying enzymes in cell suspension cultures, shoot culturea and leaves of Digitalis lanata - Stuhlemmer, Ursel; Kreis, Wolfgang (Plant Physiology and Biochemistry, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dbio.LPB.carden

Cardenolide genin pattern in Isoplexis plants and shoot cultures. - Schaller, Frank; Kreis, Wolfgang (Planta Medica, 2006)
An HPLC method for the quantitative analysis of cardenolides was developed and applied. The procedure was optimised for analysing small samples (40 mg dw) of plant and tissue culture material. Isoplexis canariensis plants obtained from seeds accumulated cardenolides to about 20-40 μmol g-1 dw as calculated from the levels of cardenolide genins released after acidic hydrolysis of methanolic extracts. The relative contents of xysmalogenin, digitoxigenin, uzarigenin and canarigenin were 5-15%, 0-5%, 10-15% and 70-90%, respectively. Shoot cultures were initiated from seeds, established as permanent cultures and cultivated on agar-solidified or in liquid medium. Shoot cultures maintained on solid medium contained an average of about 6 μmol cardenolides g-1 dw. A relatively high proportion of digitoxigenin was found in two-thirds of the shoot cultures examined. The cardenolide content of amphibian shoot cultures averaged to about 1 μmol g-1 dw. Plants regenerated from shoot cultures and maintained under hydroponic conditions accumulated the same amount of cardenolides as plants collected in the field. No cardenolides could be detected in callus cultures. © Georg Thieme Verlag KG Stuttgart.
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.carden
Keywords: Callus culture; Canarigenin; Cardenolides; Cardiac glycosides; Dianhydroperiplogenin; Digitoxigenin; Hydroponics; Isoplexis canariensis; Plantaginaceae; Shoot culture; Uzarigenin; Xysmalogenin

Cardenolide Glucosyltransferases and Glucohydrolases in Leaves and Cell Cultures of Three Digitalis (Scrophulariaceae) Species - Kreis, Wolfgang; May, Ursula (Journal of Plant Physiology, 1990)
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.carden

Cardiac Glycoside Glucoevatromonoside Induces Cancer Type-specific Cell Death - Schneider, Naira F. Z.; Cerella, Claudia; Lee, Jin-Young; Mazumder, Aloran; Kim, Kyung Rok; de Carvalho, Annelise; Munkert, Jennifer; De Padua, Rodrigo Maia; Kreis, Wolfgang; Kim, Kyu-Won; Christov, Christo; Dicato, Mario; et al. (Frontiers in Pharmacology, 2018)

Cardiac Glycosides in Partly Submerged Shoots of Digitalis lanata. - Stuhlemmer, Ursel; Kreis, Wolfgang; Eisenbeiß, Marina; Reinhard, Ernst (Planta Medica, 1993)
Shoot cultures were established from axillary buds (11 strains) or seeds (1 strain) of individual Digitalis lanata Ehrh. plants and propagated partially submerged in liquid medium. Five of these shoot culture strains were characterized with regard to their growth and cardenolide content. The cultures were observed for more than one year and found to be relatively stable with regard to their growth and cardenolide spectrum and yield. The strains examined differed in terms of their total cardenolide yield, which ranged from about 30 nmol g DW-1 to almost 1000 nmol g DW-1. Cardenolide content was correlated with leaf size and development. Depending on the strain investigated up to ten different cardenolides could be detected by HPLC. The main cardenolides were identified by comparing HPLC and TLC results with those of authentic samples and chemical degradation as being the mono- and diglycosides glucodigifucoside, glucoverodoxin, odorobioside G, and odoroside H; minor amounts of digitalinum verum and glucoevatromonoside were also found. In addition, the tetrasaccharides lanatoside A and C were present. The shoots were cardenolide-free when cultivated in the dark for more than 30 weeks, but regained their characteristic cardenolide profile when transferred back to light. For the dark cultivation of chlorophyll-free cultures a medium containing 3.5% glucose was found to be optimal.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.cardia
Keywords: cardenolides; Digitalis lanata; Scrophulariaceae; shoot culture

Catecholamine biosynthesis dependent on the dark in betacyanin-forming Portulaca callus - Endress, Rudolf; Jäger, Alexander; Kreis, Wolfgang (Journal of Plant Physiology, 1984)

Cellular organization of cardenolide biotransformation in Digitalis grandiflora Mill. - Kreis, Wolfgang; Hoelz, Hubert; Sutor, Renate; Reinhard, Ernst (Planta, 1993)
The cellular compartmentalization of cardenolide biotransformation in Digitalis grandiflora Mill. cell cultures was investigated. The presence of UDP-glucose: digitoxin 16′-O-glucosyltransferase (DGT; EC 2.4.1.-), acetyl-CoA: digitoxin 15′-O-acetyltransferase (DAT; EC 2.3.1.-) and cardenolide 16′-O-glucohydrolase (CGH; EC 3.2.1.21) was demonstrated and their time courses during one cell culture cycle were established. The activities of DGT, DAT and CGH were quite constant over time and leveled off at around 3, 30 and 100 ukat, respectively, per kg protein. The cardenolide products formed by DGT action were shown to be exclusively localized in the central vacuole. The cellular distributions of DGT, CGH and unspecific β-glucosidase were investigated and it was shown that DGT and CGH are not localized in the vacuoles, whereas unspecific glucosidase is. The influence on cardenolide uptake of the set of biotransformation enzymes present in a given cell line is discussed. An updated cellular model of cardenolide biotransformation is proposed. © 1993 Springer-Verlag.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.cellul
Keywords: Acetylesterase; Acetyltransferase; Biotransformation; Cardiac glycoside (compartmentalization); Digitalis; Glucosyltransferase; Vacuole

Clonal propagation of Isoplexis canariensis - Schaller, Frank; Kreis, Wolfgang (Planta Medica, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dbio.LPB.clonal

Crystallization and preliminary crystallographic analysis of selenomethoionine-labelled progesterone 5β-reductase from Digitalis lanata Ehrh. - Egerer-Sieber, Claudia; Herl, Vanessa; Müller-Uri, Frieder; Kreis, Wolfgang; Muller, Yves (Acta Crystallographica Section F: Structural Biology and Crystallization Communications, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.crysta

Curcumin in der Krebstherapie - Bauer, Peter; Kreis, Wolfgang (Deutsche Zeitschrift für Onkologie, 2011)

Cytotoxic and cytostatic effects of digitoxigenin monodigitoxoside (DGX) in human lung cancer cells and its link to Na,K-ATPase - Schneider, Naira F. Z.; Persich, Lara; Rocha, Sayonarah C.; Ramos, Ana Carolina Pacheco; Cortes, Vanessa Faria; Silva, Izabella Thais; Munkert, Jennifer; De Padua, Rodrigo Maia; Kreis, Wolfgang; Taranto, Alex G.; Barbosa, Leandro A.; Braga, Fernão Castro; et al. (Biomedicine & Pharmacotherapy, 2017)

Cytotoxic effects of the cardenolide convallatoxin and its Na,K-ATPase regulation - Schneider, Naira F. Z.; Silva, Izabella Thais; Persich, Lara; de Carvalho, Annelise; Rocha, Sayonarah C.; Marostica, Lucas L.; Ramos, Ana Carolina Pacheco; Taranto, Alex G.; De Padua, Rodrigo Maia; Kreis, Wolfgang; Barbosa, Leandro A.; Braga, Fernão Castro; et al. (Molecular and Cellular Biochemistry, 2017)

Cytotoxicity of AMANTADIG - a semisynthetic digitoxigenin derivative - alone and in combination with docetaxel in human hormone-refractory prostate cancer cells and its effect on Na+/K+ -ATPase inhibition. - Silva, Izabella Thais; Munkert, Jennifer; Nolte, Elke; Schneider, Naira F. Z.; Rocha, Sayonarah C.; Ramos, Ana Carolina Pacheco; Kreis, Wolfgang; Braga, Fernão Castro; De Padua, Rodrigo Maia; Taranto, Alex G.; Cortes, Vanessa Faria; Barbosa, Leandro A.; et al. (Biomedicine & Pharmacotherapy, 2018)
Keywords: Prostate cancer; AMANTADIG; docetaxel; synergistic effects; Na+/K+ -ATPase; docking studies

Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Zanchett Schneider, Naira Fernanda; Menegaz, Danusa; Andreotti Dagostin, Andre Luiz; Persich, Lara; Rocha, Sayonarah C.; Pacheco Ramos, Ana Carolina; Cortes, Vanessa Faria; Leite Fontes, Carlos Frederico; De Padua, Rodrigo Maia; Munkert, Jennifer; Kreis, Wolfgang; Braga, Fernao Castro; et al. (Molecular and Cellular Biochemistry, 2021)
Cardiac glycosides (CGs) are useful drugs to treat cardiac illnesses and have potent cytotoxic and anticancer effects in cultured cells and animal models. Their receptor is the Na+,K+ ATPase, but other plasma membrane proteins might bind CGs as well. Herein, we evaluated the short- and long-lasting cytotoxic effects of the natural cardenolide glucoevatromonoside (GEV) on non-small-cell lung cancer H460 cells. We also tested GEV effects on Na+,K+ -ATPase activity and membrane currents, alone or in combination with selected chemotherapy drugs. GEV reduced viability, migration, and invasion of H460 cells spheroids. It also induced cell cycle arrest and death and reduced the clonogenic survival and cumulative population doubling. GEV inhibited Na+,K+-ATPase activity on A549 and H460 cells and purified pig kidney cells membrane. However, it showed no activity on the human red blood cell plasma membrane. Additionally, GEV triggered a Cl-mediated conductance on H460 cells without affecting the transient voltage-gated sodium current. The administration of GEV in combination with the chemotherapeutic drugs paclitaxel (PAC), cisplatin (CIS), irinotecan (IRI), and etoposide (ETO) showed synergistic antiproliferative effects, especially when combined with GEV + CIS and GEV + PAC. Taken together, our results demonstrate that GEV is a potential drug for cancer therapy because it reduces lung cancer H460 cell viability, migration, and invasion. Our results also reveal a link between the Na+,K+-ATPase and Cl- ion channels.
CRIS-Team WoS Importer:2021-02-12

Delta5-3beta-hydroxysteroid dehydrogenase delta5/delta4-ketosteroid isomerase (3beta-HSD), a possible enzyme of cardiac glycoside biosynthesis, in cell cultures and plants of Digitalis lanata Ehrh. - Seidel, Stefanie; Kreis, Wolfgang; Reinhard, Ernst (Plant Cell Reports, 1990)
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.delta5

Development and validation of a quick assay for the total glucosinolate content in horseradish (Armoracia rusticana) using glucose strips and a blood glucose meter - Meitinger, Nadine; Kreis, Wolfgang (Journal of Applied Botany and Food Quality-Angewandte Botanik, 2018)
A quick assay to determine the total glucosinolate content of fresh horseradish roots in less than 10 minutes is described. The method involves the following steps: 1. Maceration of horseradish root with 4% phosphoric acid to avoid enzymatic degradation of endogenous glucosinolates, 2. neutralization of the extract and determination of free glucose using a commercial blood glucose meter, 3. enzymatic hydrolysis of the glucosinolates by exogenous myrosinase, 4. detection of released glucose, again using a blood glucose meter, and 5. calculation of the glucosinolate content on the basis of the difference between the two glucose values determined. The newly developed assay (‘ITC quick test’) was compared with a standard high-performance liquid chromatographic method for glucosinolate analysis. Armoracia rusticana<br

Die Mistel in der Tumortherapie 3. Aktueller Stand der Forschung und klinische Anwendung - Scheer, Rainer; Alban, Susanne; Becker, Hans; Blaschek, Wolfgang; Kemper, Fritz; Kreis, Wolfgang; Matthes, Harald; Schilcher, Heinz; Stange, Rainer (KVC Verlag, 2013)

Die Mistel in der Tumortherapie 5, aktueller Stand der Forschung und klinische Anwendung - Scheer, Rainer; Alban, Susanne; Becker, Hans; Beer, André-Michael; Blaschek, Wolfgang; Klein, Reinhild; Kreis, Wolfgang; Leneweit, Gero; Matthes, Harald; Spahn, Günther; Stange, Rainer (KVC Verlag, 2020)

Digitalis - Clemente, Ester Sales; Müller-Uri, Frieder; Nebauer, Sergio G.; Segura, Juan; Kreis, Wolfgang; Arrillaga, Isabel (Wild Crop Relatives: Genomic and Breeding Resources, Plantaton and Ornamental Crops, 2011)
UnivIS-Import:2015-04-20:Pub.2011.nat.dbio.LPB.digita

Does Malonyl coenzyme A:Hydroxypregnane 21-Hydroxymalonyltransferase catalyze the first step in butenolide ring formation? - Stuhlemmer, Ursel; Kreis, Wolfgang (Tetrahedron Letters, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dbio.LPB.doesma

Effect of Digitalis lanata matrix composition on the lanatoside C partition coefficient and its consequence on rotation locular counter-current chromatography efficiency - Braga, Fernão C.; Kreis, Wolfgang; Braga de Oliveira, Alaíde (Journal of Chromatography A, 1998)
Lanatoside C standard samples had their partition coefficients (K) determined in dichloromethane-methanol-water (4:4:3), (5:6:4) and (7:13:8), by the shake flask method and the obtained values were similar. On the other hand, K for lanatoside C accomplished by calculation from rotation locular counter-current chromatography (RLCC) traces of Digitalis lanata pre-purified extracts, as well as by the shake flask method, in the same solvent systems, showed a significant variation. Such variation was attributed to differences in the pre-purification procedures for D. lanata extract, which resulted in starting materials for RLCC with very distinct cardenolide profiles, reflecting, thus, in the K values for lanatoside C and, consequently, in the lanatoside C purity at the end of the chromatographic process. Copyright (C) 1998 Elsevier Science B.V.
UnivIS-Import:2015-03-05:Pub.1998.nat.dbio.LPB.effect_92
Keywords: Cardenolides; Counter-current chromatography; Digitalis lanata; Lanatosides; Matrix effects; Partition coefficients

Effects of digitoxigenin, digoxigenin, and various cardiac glycosides on cardenolide accumulation in shoot cultures of Digitalis lanata - Theurer, Christoph; Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dbio.LPB.effect_86

Effects of Lipophilicity and Structural Features on the Antiherpes Activity of Digitalis Cardenolides and Derivatives - De Padua, Rodrigo Maia; Kratz, Jadel Muller; Munkert, Jennifer; Bertol, Jessica Wildgrube; Rigotto, Caroline; Schuster, Daniela; Maltarollo, Vinicius Goncalves; Kreis, Wolfgang; Oliveira Simoes, Claudia Maria; Braga, Fernao Castro (Chemistry & Biodiversity, 2022)
There is growing interest in exploring Digitalis cardenolides as potential antiviral agents. Hence, we herein investigated the influence of structural features and lipophilicity on the antiherpes activity of 65 natural and semisynthetic cardenolides assayed in vitro against HSV-1. The presence of an α,β-unsaturated lactone ring at C-17, a β-hydroxy group at C-14 and C-3β-OR substituents were considered essential requirements for this biological activity. Glycosides were more active than their genins, especially monoglycosides containing a rhamnose residue. The activity enhanced in derivatives bearing an aldehyde group at C-19 instead of a methyl group, whereas inserting a C-5β-OH improved the antiherpes effect significantly. The cardenolides lipophilicity was accessed by measuring experimentally their log P values (n-octanol-water partition coefficient) and disclosed a range of lipophilicity (log P 0.75±0.25) associated with the optimal antiherpes activity. In silico studies were carried out and resulted in the establishment of two predictive models potentially useful to identify and/or optimize novel antiherpes cardenolides. The effectiveness of the models was confirmed by retrospective analysis of the studied compounds. This is the first SAR study addressing the antiherpes activity of cardenolides. The developed computational models were able to predict the active cardenolides and their log P values.
CRIS-Team Scopus Importer:2022-10-14
Keywords: antiherpes activity; antiviral agents; structure-activity relationship; cardenolides; in silico studies; log P

Effects of various pregnanes and two 23-nor-5-cholenic acids on cardenolide accumulation in cell and organ cultures of Digitalis lanata EHRH - Haussmann, Werner; Kreis, Wolfgang; Stuhlemmer, Ursel; Reinhard, Ernst (Planta Medica, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.effect

Elektrofusion von Protoplasten aus Digitalis lanata Ehrh. und Digitalis purpurea L. Suspensionskulturen unter Mikrogravitation. Vergleich der enzymatischen Eigenschaften der regenerierten Zellinien. - Baumann, T; Kreis, Wolfgang; Mehrle, W; Hampp, R; Reinhard, Ernst (Statusseminar Forschung unter Weltraumbedingungen, 1991)
UnivIS-Import:2015-04-16:Pub.1991.nat.dbio.LPB.elektr

Elucidation of the mechanism of anti-herpes action of two novel semisynthetic cardenolide derivatives. - Boff, Laurita; Schneider, Naira Fernanda Zanchett; Munkert, Jennifer; Ottoni, Flaviano Melo; Ramos, Gabriela Silva; Kreis, Wolfgang; Braga, Fernao Castro; Alves, Ricardo José; Maia de Pádua, Rodrigo; Simões, Cláudia M. O. (Archives of Virology, 2020)
Human herpesviruses are among the most prevalent pathogens worldwide and have become an important public health issue. Recurrent infections and the emergence of resistant viral strains reinforce the need of searching new drugs to treat herpes virus infections. Cardiac glycosides are used clinically to treat cardiovascular disturbances, such as congestive heart failure and atrial arrhythmias. In recent years, they have sparked new interest in their potential anti-herpes action. It has been previously reported by our research group that two new semisynthetic cardenolides, namely C10 (3β-[(N-(2-hydroxyethyl)aminoacetyl]amino-3-deoxydigitoxigenin) and C11 (3β-(hydroxyacetyl)amino-3-deoxydigitoxigenin), exhibited potential anti-HSV-1 and anti-HSV-2 with selectivity index values > 1,000, comparable with those of acyclovir. This work reports the mechanism investigation of anti-herpes action of these derivatives. The results demonstrated that C10 and C11 interfere with the intermediate and final steps of HSV replication, but not with the early stages, since they completely abolished the expression of the UL42 (β) and gD (γ) proteins and partially reduced that of ICP27 (α). Additionally, they were not virucidal and had no prophylactic effects. Both compounds inhibited HSV replication at nanomolar concentrations, but cardenolide C10 was more active than C11 and can be considered as an anti-herpes drug candidate including against acyclovir-resistant HSV-1 strains.

Enzymatic Degradation of Cichoric Acid in Echinacea purpurea Preparations - Nüßlein, Birgit; Kurzmann, Michael; Bauer, Rudolf; Kreis, Wolfgang (Journal of Natural Products, 2000)
Cichoric acid (2R,3R-O-dicaffeoyltartaric acid) (1) is highly susceptible to enzymatic degradation during the preparation of Echinacea purpurea products. Degradation of 1 and other caffeic acid derivatives can be inhibited by antioxidants added to the extraction solvent or in buffered protein extracts saturated with nitrogen. Inhibitor studies conducted with protein extracts prepared from dried overground parts of E. purpurea revealed that polyphenol oxidases (PPO) but not peroxidases are responsible for the oxidative degradation of exogenous and endogenous caffeic acid derivatives. With a view to stabilizing aqueous extracts with respect to their content of 1, the effects of ascorbic acid and ethanol were tested. Compound 1 was not stable under conditions where oxidative processes could almost be excluded. It was found that an esterase hydrolyzing the ester bonds between tartaric acid and caffeic acid is still active under PPO inhibitory conditions. Finally, addition of 40% ethanol and 50 mM ascorbic acid to aqueous extracts of "Echinaceae purpureae herba" resulted in a constant amount of cichoric acid over four weeks.
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.enzyma

Enzyme bei der Gewinnung von Drogen und der Herstellung von Phytopharmaka - Kreis, Wolfgang (Pharmakognosie - Phytopharmazie, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dbio.LPB.enyzme

Enzyme bei der Gewinnung von Drogen und der Herstellung von Phytopharmaka. - Kreis, Wolfgang (Pharmakognosie - Phytopharmazie, 2010)
UnivIS-Import:2015-04-20:Pub.2010.nat.dbio.LPB.enzyme

Exploiting enzyme promiscuity to shape plant specialized metabolism - Kreis, Wolfgang; Munkert, Jennifer (Journal of Experimental Botany, 2019)
The amazing variability of plant metabolism and its rapid divergence during evolution pose fundamental questions as to the driving forces, mechanisms and players in metabolic differentiation. This review examines concepts that help us understand adaptive pathway evolution, with a particular emphasis on plant specialized metabolism, previously often termed secondary metabolism. Following a general introduction to pathway and metabolite evolution the focus is directed to enzyme promiscuity and its classification. Promiscuous enzymes (or substrates), ‘silent’ elements of the metabolome and the metabolic underground, may be used and combined to evolve ‘new’ metabolic pathways. It appears that new pathways are rarely designed from scratch, but instead emerge from ‘floppy’ enzymes and elements of a ‘messy’ metabolism, in this way generating a range of metabolites some of which may provide benefits to the plant.<br
Keywords: biological messiness; enzyme promiscuity; metabolic diversication; natural products; pathway evolution; silent metabolism; specialized metabolism; underground metabolism

Exploiting plant cell culture for natural product formation - Kreis, Wolfgang (Journal of Applied Botany and Food Quality-Angewandte Botanik, 2019)
The initiation of callus cultures and in vitro cultivation of plant cells, even in large bioreactors, has become a routine task. Despite the fact, that permanent cell and organ cultures can produce a whole range of small natural compounds (SNAPs) used in medicine, only a few could be produced at commercial scale. However, plant cell cultures provide very useful systems to study the biosynthetic pathways leading to SNAPs at the enzyme and gene level. They turned out to be ‘a pot of gold’ for those chasing the enzymes and genes involved in natural product formation. The use of genetically modified yeast and bacteria for the production of SNAPs is an emerging technique that will take research into the coming decades. This review contemplates and revisits developments in the field of using plant cell and tissue culture as tools to elucidate SNAP formation and means to produce bioactive plant natural products over the past 40 years alongside my own wor

Expression, crystallization and structure elucidation of γ-terpinene synthase from Thymus vulgaris - Rudolph, Kristin; Parthier, Christoph; Egerer-Sieber, Claudia; Geiger, Daniel; Muller, Yves; Kreis, Wolfgang; Müller-Uri, Frieder (Acta Crystallographica Section F: Structural Biology and Crystallization Communications, 2016)

Extracellular polysaccharides produced by suspension-cultured cells from Digitalis lanata - Hensel, Andreas; Schmidgall, Jörg; Kreis, Wolfgang (Planta Medica, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.extrac

Fortschritte bei der Strukturaufklärung von Inhaltsstoffen der Mistel - Kreis, Wolfgang (Die Mistel in der Tumortherapie 2. Aktueller Stand der Forschung und klinische Anwendung., 2009)
UnivIS-Import:2015-05-08:Pub.2009.nat.dbio.LPB.fortsc

GLC-MS investigations on cardenolide genins - Hensel, Andreas; Kreis, Wolfgang (Pharmaceutica Acta Helvetiae, 1997)
A new GLC-MS method for the separation and identification of cardenolide acetates in hydrolyzed plant extracts was established. The method was shown to be selective and linear in the range from 10 μg to 5 mg/ml. Detection limits in a selected ion modus (SIM) were determined to be 5 μg/ml for digitoxigenin acetate, digoxigenin diacetate and diginatigenin triacetate and 1 μg/ml for gitoxin diacetate. Recovery rates were determined to be 96%. MS-fragmentation revealed that cardenolides with different hydroxylation patterns can be differentiated by using distinct mass fragments as indicators. While 12β-hydroxylated cardenolides are characterized by m/z 201 and 229, cardenolides without this function fragment mainly to m/z 203 and 231. Δ5,6-unsaturated cardenolides (xysmalogenin acetate) or 5α-cardenolides (uzarigenin acetate) show fragmentation patterns similar to those of saturated or 5β-cardenolides.
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.glcmsi
Keywords: Cardenolides; GC-MS; Validation

Glycosylation in cardenolide biosynthesis. - Theurer, Christoph; Treumann, Hans-Joachim; Faust, Thomas; May, Ursula; Kreis, Wolfgang (Plant Cell Tissue and Organ Culture, 1994)
The glycosylation and deglycosylation of cardiac glycosides was investigated using cell suspension cultures and shoot cultures, both established from Digitalis lanata EHRH. plants, as well as isolated enzymes. Shoots were capable of glucosylating digitoxigenin, evatromonoside, digiproside, glucodigitoxigenin and digitoxin. Suspension cultured Digitalis cells glucosylated all the substrates mentioned but digiproside, whereas the UDP-glucosedependent cardinolide glucosyltransferase isolated from that source did not accept digitoxigenin and digiproside as substrates. It is concluded that at least three different glucosyltransferases are involved in cardiac glycoside formation in Digitalis. Similar experiments carried out with glucosylated cardenolides which were administered to cultured cells, shoots and a cardenolide β-glucosidase isolated from young leaves revealed that at least two different glucosidases occur in Digitalis lanata, albeit in different tissues or during different phases of development. The biotransformation of glucoevatromonoside was investigated using unlabelled compound and [14C-glucose]-glucoevatromonoside synthesized enzymatically. After 7 d of incubation almost no radioactivity could be recovered from the cardenolide fraction, indicating that the terminal glucose of glucoevatromonoside was now incorporated into volatile, hydrophilic and insoluble compounds. Since, on the other hand, large amounts of cardenolides were found in the experiments with unlabelled glucoevatromonoside it is assumed that steady state or pool size regulation is achieved by the coordinated action of a cardenolide glucosidase and a glucosyltransferase. © 1994 Kluwer Academic Publishers.
UnivIS-Import:2015-03-05:Pub.1994.nat.dbio.LPB.glycos
Keywords: β-glucosidase; biotransformation; cardiac glycosides; Digitalis lanata; glucosyltransferase; radiolabelled cardiac glycosides

Herzglykoside und ihr Potenzial für die Tumortherapie - Munkert, Jennifer; Kreis, Wolfgang (Deutsche Zeitschrift für Onkologie, 2017)

Highly conserved progesterone 5β-reductase (P5βR) genes, from 5β-cardenolide-free and 5β-cardenolide-producing angiosperms. - Bauer, Peter; Munkert, Jennifer; Brydziun, Margareta; Burda, Edyta; Müller-Uri, Frieder; Gröger, Harald; Muller, Yves; Kreis, Wolfgang (Phytochemistry, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dbio.LPB.highly

Highly Efficient 12β-Hydroxylation of Digitoxin in Digitalis lanata Cell Suspensions Using a Two-staged Culture Method - Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1986)

Identification and stress-induced expression of three 3β-hydroxysteroid dehydrogenases from Erysimum crepidifolium Rchb. and their putative role in cardenolide biosynthesis - Munkert, Jennifer; Ernst, Mona; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2014)

Identifying structural features for changing substrate preferences in two Plantago PRISEs (pro-gesterone 5 beta-reductase and / or iridoid synthase) - Dorfner, Maja; Klein, J.; Lanig, Harald; Kreis, Wolfgang; Munkert, Jennifer (PLANTA MEDICA, 2021)
Cardenolides are drugs used to treat congestive heart failure. Recently their antiproliferative action was brought back into focus [1]. They are still extracted from plants, as their chemical structure impedes chemical synthesis. Though attempts have been made to produce cardenolides by plant tissue culture, farming foxglove still remains the sole source of cardenolides with a possible alternative approach based on microbial production systems. So far we engineered yeast and E. coli to produce intermediate products of cardenolide biosynthesis but still need to overcome enzyme bottlenecks [2]. Targets of enzyme engineering are the PRISEs (progesterone-5β-reductase/iridoid synthase-like enzymes), that catalyzes the reduction of progesterone to 5β-pregnane-3,20-dione, which is an important intermediate of cardenolide biosynthesis. PRISEs occur ubiquitously in the plant kingdom [3] and are enzymes with relaxed substrate specificity [4]. In biotechnology shaping enzymes with respect to their substrate specificity is a useful approach to optimize biosynthetic pathways. Thus, to overcome substrate shortages, we investigated substrate conversion in silico and in vitro of two Plantago PRISEs by creating mutants via site-directed mutagenesis. A PRISE of P. media showed a 70-fold higher specific activity with progesterone than its orthologue from P. lanceolata. Docking substrates into mutants prior to the site-directed mutagenesis, was used as additional tool to identify catalytically impactful residues, so that we were able to completely invert the substrate specificities of the two Plantago PRISEs for progesterone. Engineering substrate specificity into promiscuous enzymes may not only help to eliminate side reactions in biosynthetic pathway but also to understand metabolite-enzyme evoluti
CRIS-Team WoS Importer:2021-12-31

Immobilization of Flavonol 3-O-beta-Heterodisaccharidase on Porous Glass and Production of Rutinose from Rutin. - Coniglio, Marcela; Kreis, Wolfgang (Planta Medica, 2009)
Flavonol 3-O-β-heterodisaccharidase (FHG 1) was isolated from the dried herb of Fagopyrum esculentum, immobilized on porous glass, and used for the release of rutinose from rutin. The stability of the enzyme in its free or immobilized form was observed continuously at two different temperatures (4 °C and 25°C). T1/2 values were determined to be about 48 h for the free enzyme and about 300 h for the immobilized enzyme. The rutinose released was isolated by fractionated ethanol precipitation.
UnivIS-Import:2015-03-09:Pub.2009.nat.dbio.LPB.immobi
Keywords: Disaccharidase; Enzyme immobilization; Fagopyrum esculentum; Polygonaceae; Rutin; Rutinose

Influence of precursors and inhibitors of the sterol pathway on sterol and cardenolide metabolism in Digitalis lanata EHRH - Milek, Frank; Reinhard, Ernst; Kreis, Wolfgang (Plant Physiology and Biochemistry, 1997)
The influence of 25-azacycloartanol, an inhibitor of SAM:cycloartenol 24-methyltransferase, and cyproconazole, an experimental triazole known to inhibit ergosterol biosynthesis in fungi, on cardenolide and phytosterol accumulation was studied in different Digitalis lanata Ehrh, tissue cultures. The influence of various steroids was also examined. Cardenolide-producing as well as cardenolide-free tissue cultures contained free cholesterol, sitosterol, campesterol and stigmasterol. Stigmasterol was the predominant sterol in cardenolide-producing cultures, whereas sitosterol dominated in cardenolide-free tissues. Suspension-cultured cells had the highest sterol content of the materials analyzed. Cardenolides and 24-alkyl sterols decreased after administration of 25-azacycloartanol, whereas the pool of free cholesterol increased. Cyproconazol influenced mainly the pools of 24-alkyl sterols and cardenolides; cholesterol contents did not change significantly. The specificity and toxicity of the inhibitors applied were evaluated. Neither the 12β-hydroxylation of β-methyldigitoxin was influenced, nor was the stimulating effect of 21-hydroxypregnenolone on cardenolide formation inhibited. The results presented support the view that 24-alkyl sterols rather than cholesterol are the favoured sterol precursors of the cardenolides in Digitalis lanata.
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.influe
Keywords: 25-azacycloartanol; cardiac glycosides; cycloartenol; cyproconazol; Digitalis lanata; inhibitors; phytosterols

Influence of the wavelength and intensity of LED lights and cytokinins on the growth rate and the concentration of total cardenolides in Digitalis mariana Boiss. ssp. heywoodii (P. Silva and M. Silva) Hinz cultivated in vitro - Da Silva, Giselly Mota; Mohamed, Alliyu; De Carvalho, Alexandre Alves; Brasil Pereira Pinto, Jose Eduardo; Braga, Fernao Castro; De Padua, Rodrigo Maia; Kreis, Wolfgang; Vilela Bertolucci, Suzan Kelly (Plant Cell Tissue and Organ Culture, 2022)
Digitalis mariana Boiss. ssp. heywoodii is a source of bioactive cardenolides like glucoevatromonoside. The aim was to investigate the in vitro propagation of D. mariana ssp. heywoodii under different cytokinin concentrations and combinations, as well as distinct light intensities and wavelengths, and their effect on plant growth and total cardenolide production. Shoots were inoculated in MS culture medium supplemented with the following 6-benzylaminopurine (BAP) + thidiazuron (TDZ) cytokinin combinations. Shoots were additionally grown under different light intensities (20, 50, 78, 102 and 139 µmol m−2 s−1 LEDs) and wavelength conditions (fluorescent, white, green, blue (B), red (R) LEDs—70%R:30%B, 30%R:70%B, 50%R:50%B). The largest number of shoots was induced at BAP + TDZ concentrations of 0.5 + 0.5; 0.25 + 0.75 and 1.0 + 0.5 mg L−1, with mean values of 8.80, 10.37 and 10.60 shoot explants−1, respectively. The combination of 0.375 + 0.125 mg L−1 of BAP + TDZ (366 mg plant−1) resulted in the highest dry leaf weight. Increased cytokinin concentrations led to a larger number of hyperhydrified shoots and decreased cardenolide production. The absence of cytokinins in the medium resulted in higher contents of total cardenolides (0.310 ± 0.008%, g/g) in leaves. However, the combination of 0.375 mg L−1 BAP + 0.125 mg L−1 TDZ increased the total cardenolide production to 82.52 ± 12.52 mg TC plantlet−1. Light intensity of 139 µmol m−2 s−1 improved plant growth and cardenolide production. With respect to the light spectrum the blue/red wavelength combination encouraged shoot biomass production and elevated total cardenolide contents.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Light-emitting diode; Photon flux density; Plantaginaceae; Propagation in vitro; Spectrophotometry

Inhibition of cell proliferation, invasion and migration by the cardenolides digitoxigenin monodigitoxoside and convallatoxin in human lung cancer cell line - Schneider, Naira F. Z.; Geller, Fabiana C.; Persich, Lara; Marostica, Lucas L.; Maia de Pádua, Rodrigo; Kreis, Wolfgang; Braga, Fernão C.; Simões, Cláudia M. O. (Natural Product Research, 2015)

In silico, in vitro, and structural investigations on BAHD-enzymes from different species able to malonylate 21-hydroxypregnanes - Tropper, Marina; Wolf, Laura-Sophie; Lanig, Harald; Kreis, Wolfgang (PLANTA MEDICA, 2021)
CRIS-Team WoS Importer:2021-12-31

Investigation of the cytotoxic activity of two novel digitoxigenin analogues on H460 lung cancer cells - Boff, Laurita; Persich, Lara; Brambila, Paula; Ottoni, Flaviano Melo; Munkert, Jennifer; Ramos, Gabriela Silva; Soares Viana, Adhônis Rodrigues; Kreis, Wolfgang; Braga, Fernão Castro; Alves, Ricardo José; Maia de Pádua, Rodrigo; Schneider, Naira Fernanda Zanchett; et al. (Anti-Cancer Drugs, 2020)
Cardiac glycosides (CGs) are natural compounds traditionally used for the treatment of heart disorders, and recently new therapeutic possibilities were proposed. Their antitumor reports and clinical trials have notably enhanced, including those targeted for lung cancer, the most lethal type that lacks of new treatment agents, instigating the research of these molecules. The CGs studied here, named C10 3β-[(N-(2-hydroxyethyl)aminoacetyl]amino-3-deoxydigitoxigenin and C18 (3β-(aminoacetyl)amino-3-deoxydigitoxigenin), are semisynthetic derivatives prepared from digitoxigenin scaffold. Both compounds demonstrated high cytotoxicity for different cancer cell lines, especially H460 lung cancer cells, and their cytotoxic effects were deeply investigated using different methodological approaches. C10 induced cell death at lower concentrations and during shorter periods of treatment than C18, and increased the number of small and irregular nuclei, which are characteristics of apoptosis. This type of cell death was confirmed by caspase-3/7 assay. Both compounds reduced H460 cells proliferative potential by long-term action, and C10 showed the strongest potential. Moreover, these compounds induced a significant decrease of the area and viability of H460 spheroids providing preclinical favorable profiles to develop new chemotherapeutic agents.
CRIS-Team Scopus Importer:2020-04-17

In vitro culturing techniques of medicinal plants. - Kreis, Wolfgang (Medicinal Plant Biotechnology. From Basic Research to Industrial Applications, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dbio.LPB.invitr

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Yücesan, Buhara; Mohammed, Aliyu; Eker, İsmail and Sameeullah, Muhammad and Demir-Ordu, Öznur and Cihangir, Cansu and Şahbaz, Nevin and Kaya, Özge and Müller-Uri, Frieder and Kreis, Wolfgang and Gürel, Ekrem (In Vitro Cellular & Developmental Biology-Plant, 2016)
Cardenolides isolated from genus Digitalis are natural compounds used in treating cardiac insufficiencies. Recent investigations have also suggested the use of cardenolides in oncology. Due to the medicinal importance of the genus Digitalis, in vitro regeneration techniques would be useful for propagating the best genotypes selected from natural sources. To achieve this, Digitalis ferruginea subsp. schischkinii (Ivanina) K. Werner was collected from different locations along the Black Sea region of Turkey. In the cardenolide analysis, samples from Giresun and Trabzon showed a greater diversity than those from other locations, and thus, the Trabzon population was selected for plant tissue culture studies. In vitro regeneration was performed using cotyledonary leaves and hypocotyl segments on Murashige and Skoog (MS) medium containing various concentrations (0.5, 1.0, or 2.0 mg L-1) of 6-benzyladenine (BA), kinetin (KIN), or thidiazuron (TDZ) alone or in combination with indole-3-acetic acid (IAA) at 0.5 or 1.0 mg L-1. Among the media used for shoot regeneration, the highest frequency of shoot organogenesis was obtained from MS medium containing 2.0 mg L-1 TDZ and 0.5 mg L-1 IAA, producing 11.0 shoots per explant with 100% regeneration frequency from hypocotyl explants after 4 wk. For successful rooting, IAA was the most effective at 1.0 or 2.0 mg L-1, producing 16.3 or 17.3 roots per shoot, respectively, after 4 wk. Regenerants from several medium types were grown in a greenhouse for 6 mo, and all displayed similar cardenolide contents, i.e., the lanatoside C level was around 0.3% (w/w) while the levels of lanatosides A and B, digoxin, and digitoxin were less than 0.08% (w/w), similar to plants grown from seeds collected from Trabzon district.
Keywords: Cardenolides; Digitalis ferruginea subsp; schischkinii; Foxglove; In vitro culture

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp. schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Yücesan, Buhara; Mohammed, Aliyu; Eker, İsmail and Sameeullah, Muhammad and Demir-Ordu, Öznur and Cihangir, Cansu and Şahbaz, Nevin and Kaya, Özge and Müller-Uri, Frieder and Kreis, Wolfgang and Gürel, Ekrem (In Vitro Cellular & Developmental Biology-Plant, 2016)

In vitro regeneration and cardenolide determination of an endemic foxglove, Digitalis cariensis (Aegean Foxglove) - Mohammed, Aliyu; Yücesan, Buhara; Demir-Ordu, Öznur; Cihangir, Cansu; Eker, İsmail and Kreis, Wolfgang and Gürel, Ekrem (In Vitro Cellular & Developmental Biology-Plant, 2015)

Iridoid Synthase Activity is Common among the Plant Progesterone 5β-Reductase Family - Munkert, Jennifer; Pollier, Jacob; Miettinen, Karel; Van Moerkercke, Alex; Payne, Richard; Müller-Uri, Frieder; Burlat, Vincent; O'Connor, Sarah E.; Memelink, Johan; Kreis, Wolfgang; Goossens, Alain (Molecular Plant, 2015)

Isolation and Characterisation of a Cysteine Protease (Phytolacain G), from Phytolacca americana Roots. - Sußner, Ursula; Abel, Gudrun; Schulte, Ralf; Kreis, Wolfgang (Planta Medica, 2004)
Protein extracts obtained from dried and fresh roots of Phytolacca americana L. (Phytolaccaceae) were examined in order to identify and characterise individual proteins. The extracts were compared with a commercial pokeweed mitogen standard using SDS polyacrylamide gel electrophoresis (SDS-PAGE). A dominant protein, present in both the extracts and the pokeweed mitogen standard, was isolated by subsequent ammonium sulphate fractionation, anion exchange chromatography, gel filtration and SDS-PAGE. In this way it was purified 140-fold with about 20% yield and 70-fold with about 13% yield from dried and fresh roots, respectively. Its molecular mass as determined by gel filtration and SDS-PAGE was estimated to be about 25 kDa. Subsequent isoelectric focussing revealed one single protein band at pH 6.0. LysC digestion of the 25 kDa protein yielded several peptides which were subjected to micro-sequencing. Comparison with published sequences revealed that the protein isolated was phytolacain G, a cysteine protease previously isolated from unripe fruits of P. americana L. The enzyme showed a high affinity towards the oxidised insulin B-chain and was completely inhibited by trans-epoxysuccinyl-L-leucylamido(4- guanidino)-butane (E64). The purified phytolacain G showed "lectin- like" activities such as haemagglutination and mitogenic effects towards human lymphocytes.
UnivIS-Import:2015-03-09:Pub.2004.nat.dbio.LPB.isolat
Keywords: Cysteine protease; Phytolacain G; Phytolacca americana; Phytolaccaceae; Pokeweed mitogen

Isolation of cardenolides from a Brazilian cultivar of Digitalis lanata by rotation locular counter-current chromatography. - Braga, Fernão Castro; Kreis, Wolfgang; Braga de Oliveira, Alaíde (Journal of Chromatography A, 1996)
Cardenolides from a Brazilian cultivar of Digitalis lanata were isolated by rotation locular countercurrent chromatography (RLCC), employing dichloromethane-methanol-water (5:6:4, v/v) as the solvent system. Highly pure lanatoside C was obtained from the Digitalis lanata hydromethanolic extract, pre-purified either by silica gel or reversed-phase chromatography.
UnivIS-Import:2015-03-05:Pub.1996.nat.dbio.LPB.isolat
Keywords: β-Acetyldigoxin; Cardenolides; Digitalis lanata; Digoxin; Glucodigifucoside; Glucoevatromonoside; Glucogitoroside; Lanatoside A; Lanatoside C; Odorobioside G; Purpureaglycoside A; Rotation locular counter-current chromatography

Knockout of arabidopsis thaliana vep1, encoding a prise (Progesterone 5β-reductase/iridoid synthase-like enzyme), leads to metabolic changes in response to exogenous methyl vinyl ketone (mvk) - Klein, Jan; Ernst, Mona; Christmann, Alexander; Tropper, Marina; Leykauf, Tim; Kreis, Wolfgang; Munkert, Jennifer (Metabolites, 2022)
Small or specialized natural products (SNAPs) produced by plants vary greatly in structure and function, leading to selective advantages during evolution. With a limited number of genes available, a high promiscuity of the enzymes involved allows the generation of a broad range of SNAPs in complex metabolic networks. Comparative metabolic studies may help to understand why—or why not—certain SNAPs are produced in plants. Here, we used the wound-induced, vein patterning regulating VEP1 (AtStR1, At4g24220) and its paralogue gene on locus At5g58750 (AtStR2) from Arabidopsis to study this issue. The enzymes encoded by VEP1-like genes were clustered under the term PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) as it was previously demonstrated that they are involved in cardenolide and/or iridoid biosynthesis in other plants. In order to further understand the general role of PRISEs and to detect additional more “accidental” roles we herein characterized A. thaliana steroid reductase 1 (AtStR1) and compared it to A. thaliana steroid reductase 2 (AtStR2). We used A. thaliana Col-0 wildtype plants as well as VEP1 knockout mutants and VEP1 knockout mutants overexpressing either AtStR1 or AtStR2 to investigate the effects on vein patterning and on the stress response after treatment with methyl vinyl ketone (MVK). Our results added evidence to the assumption that AtStR1 and AtStR2, as well as PRISEs in general, play specific roles in stress and defense situations and may be responsible for sudden metabolic shifts.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Arabidopsis thaliana; Reactive electrophile species; Specialized metabolism; Steroid reductase

Kultivierung von pflanzlichen Zellkulturen in Bioreaktoren - Kreis, Wolfgang; Reinhard, Ernst (Bioengineering, 1989)
UnivIS-Import:2015-03-05:Pub.1989.nat.dbio.LPB.kultiv

Lanatoside 15'-O-Acetylesterase form Digitalis lanata Plants and Cell Cultures - Sutor, Renate; Hoelz, Hubert; Kreis, Wolfgang (Journal of Plant Physiology, 1990)
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.lanato

Lehrbuch der Pharmazeutischen Biologie - Reinhard, Ernst; Dingermann, Theodor; Kreis, Wolfgang; Rimpler, Horst (WVG, 2001)
UnivIS-Import:2015-04-02:Pub.2001.nat.dbio.LPB.lehrbu

Lektine: Potentielle Quellen und Anwendungen - Kreis, Wolfgang (Die Mistel in der Tumortherapie 4. Aktueller Stand der Forschung und klinische Anwendung, 2016)

Molecular cloning and expression of progesterone 5β-reductase (5β-POR) from Isoplexis canariensis. - Herl, Vanessa; Fischer, Gabriele; Bötsch, Ralf; Müller-Uri, Frieder; Kreis, Wolfgang (Planta Medica, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.molecu

Molecular cloning and heterologous expression of progesterone 5β-reductase from Digitalis lanata Ehrh. - Herl, Vanessa; Fischer, Gabriele; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.molecu_5

Nicotinamide-Dependent Ene Reductases as Alternative Biocatalysts for the Reduction of Activated Alkenes - Durchschein, Katharina; Wallner, Silvia; Macheroux, Peter; Schwab, Wilfried; Winkler, Thorsten; Kreis, Wolfgang; Faber, Kurt (European Journal of Organic Chemistry, 2012)
Four NAD(P)H-dependent non-flavin ene reductases have been investigated for their ability to reduce activated C=C bonds in an asymmetric fashion by using 20 structurally diverse substrates. In comparison with flavin-dependent Old Yellow Enzyme homologues, a higher degree of electronic activation was required, because the best activities were obtained with enals and nitroalkenes rather than enones and carboxylic esters. Although FaEO from Fragaria x ananassa (strawberry) and its homologue SlEO from Solanum lycopersicum (tomato) exhibited a narrow substrate spectrum, progesterone 5β-reductase (At5β-StR) from Arabidopsis thaliana (thale cress) and leukotriene B 4 12-hydroxydehydrogenase (LTB 4DH/PGR) from Rattus norvegicus (rat) appear to be promising candidates, in particular for the asymmetric bioreduction of open-chain enals, nitroalkenes and α,β-unsaturated γ-butyrolactones. Competing nitro reduction and non-enzymatic Weitz-Scheffer epoxidation were largely suppressed. Electronically activated alkenes have been stereoselectively reduced by using a single-enzyme-cofactor system employing nicotinamide-dependent non-flavin ene reductases. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2012.nat.dbio.LPB.nicoti
Keywords: Alkenes; Biotransformations; Enzymes; Reduction

Norcholanic acids as substrates for recombinant 3β-hydroxysteroid dehydrogenase and progesterone 5β-reductase, enzymes of the 5β-cardenolide biosynthesis - Schebitz, Pia; Nothdurft, Lars; Hensel, Andreas; Müller-Uri, Frieder; Kreis, Wolfgang (Tetrahedron Letters, 2009)
UnivIS-Import:2015-03-09:Pub.2010.nat.dbio.LPB.norcho

Overexpression and RNAi-mediated Knockdown of Two 3β-hydroxy-Δ5-steroid dehydrogenase Genes in Digitalis lanata Shoot Cultures Reveal Their Role in Cardenolide Biosynthesis - Leykauf, Tim; Klein, Jan; Ernst, Mona; Dorfner, Maja; Ignatova, Anastasiia; Kreis, Wolfgang; Lanig, Harald; Munkert, Jennifer (Planta Medica, 2023)
3β-hydroxy-Δ5-steroid dehydrogenases (3βHSDs) are supposed to be involved in 5β-cardenolide biosynthesis. Here, a novel 3βHSD (Dl3βHSD2) was isolated from Digitalis lanata shoot cultures and expressed in E. coli. Recombinant Dl3βHSD1 and Dl3βHSD2 shared 70% amino acid identity, reduced various 3-oxopregnanes and oxidised 3-hydroxypregnanes, but only rDl3βHSD2 converted small ketones and secondary alcohols efficiently. To explain these differences in substrate specificity, we established homology models using borneol dehydrogenase of Salvia rosmarinus (6zyz) as the template. Hydrophobicity and amino acid residues in the binding pocket may explain the difference in enzyme activities and substrate preferences. Compared to Dl3βHSD1, Dl3βHSD2 is weakly expressed in D. lanata shoots. High constitutive expression of Dl3βHSDs was realised by Agrobacterium-mediated transfer of Dl3βHSD genes fused to the CaMV-35S promotor into the genome of D. lanata wild type shoot cultures. Transformed shoots (35S:Dl3βHSD1 and 35S:Dl3βHSD2) accumulated less cardenolides than controls. The levels of reduced glutathione (GSH), which is known to inhibit cardenolide formation, were higher in the 35S:Dl3βHSD1 lines than in the controls. In the 35S:Dl3βHSD1 lines cardenolide levels were restored after adding of the substrate pregnane-3,20-dione in combination with buthionine-sulfoximine (BSO), an inhibitor of GSH formation. RNAi-mediated knockdown of the Dl3βHSD1 yielded several shoot culture lines with strongly reduced cardenolide levels. In these lines, cardenolide biosynthesis was fully restored after addition of the downstream precursor pregnan-3β-ol-20-one, whereas upstream precursors such as progesterone had no effect, indicating that no shunt pathway could overcome the Dl3βHSD1 knockdown. These results can be taken as the first direct proof that Dl3βHSD1 is indeed involved in 5β-cardenolide biosynthesis.<br

Overexpression of 3 beta-hydroxysteroid dehydrogenases in Digitalis lanata shoot cultures - Leykauf, Tim; Klein, J.; Lodel, M.; Kreis, Wolfgang; Munkert, Jennifer (PLANTA MEDICA, 2021)
CRIS-Team WoS Importer:2021-12-31

Partial purification and characterization of the cell-wall-associated lanatoside 15`-O-acetyltransferase from Digitalis lanata suspension cultures. - Sutor, Renate; Kreis, Wolfgang (Plant Physiology and Biochemistry, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dbio.LPB.partia

Pharmakotherapie von ADHD - Biologische Grundlagen und Grenzen - Kreis, Wolfgang (Nervenheilkunde, 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dbio.LPB.pharma

Photoconverting nets affect plant growth and levels of antiviral glucoevatromonoside and total cardenolides in Digitalis mariana ssp. heywoodii (P. Silva and M. Silva) Hinz - Marafeli, Érica Alves Marques; Chibli, Lucas Apolinário; Rocha, João Pedro Miranda; Assis, Rafael Marlon Alves de; Pinto, José Eduardo Brasil Pereira; Pádua, Rodrigo Maia de; Kreis, Wolfgang; Munkert, Jennifer; Braga, Fernão Castro; Bertolucci, Suzan Kelly Vilela (Industrial Crops and Products, 2023)
Digitalis mariana ssp. heywoodii (P. Silva & M. Silva) Hinz is an important source of bioactive cardenolides, including the promising antiviral agent glucoevatromonoside (GEV). The influence of light on the contents of total cardenolides has been demonstrated for different species of Digitalis. This study evaluated the influence of light spectral quality on the vegetative growth and levels of photosynthetic pigments, total proteins, total cardenolides, and GEV in D. mariana ssp. heywoodii. The process of extraction and quantification of GEV was established using an analytical quality by design (AQbD) approach, applying experimental design and analytical validation. Seedlings were grown for 120 days under photoconverting nets with 50% shading in blue, red, and black colours and under full sun. The use of blue net, followed by red net, resulted in the highest contents of GEV, total cardenolides, proteins, photosynthetic pigments and dry matter in the plants, along with highest root length and leaf area. The advantage of using blue nets over full sun for cultivating D. mariana ssp. heywoodii, herein demonstrated, aggregates new information on the management of this subspecies and corroborates previous data reported for other Digitalis species.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Antiviral cardenolide; Digitalis; Farming systems; Photosynthetic pigments; Spectral quality of light

Phylogeny of Anatolian (Turkey) species in the Digitalis sect. Globiflorae (Plantaginaceae) - Eker, İsmail and Yücesan, Buhara and Sameeullah, Muhammad and Welß, Walter and Müller-Uri, Frieder and Gürel, Ekrem and Kreis, Wolfgang (Phytotaxa, 2016)

Plant cell, tissue and organ cultures as tools for elucidating biosynthetic pathways. - Kreis, Wolfgang (Society for Medicinal Plant Research 50 years. A Jubilee Edition, 2003)
UnivIS-Import:2015-04-16:Pub.2003.nat.dbio.LPB.plantc

Potential anti-herpes and cytotoxic action of novel semisynthetic digitoxigenin-derivatives - Boff, L.; Munkert, Jennifer; Ottoni, F. M.; Zanchett Schneider, N. F.; Ramos, G. S.; Kreis, Wolfgang; De Andrade, S. F.; Dias De Souza Filho, J.; Castro Braga, F.; Alves, R. J.; Maia De Padua, R.; Simões, Cláudia M. O. (PLANTA MEDICA, 2019)
CRIS-Team WoS Importer:2020-01-10

Potential anti-herpes and cytotoxic action of novel semisynthetic digitoxigenin-derivatives - Boff, Laurita; Munkert, Jennifer; Ottoni, Flaviano Melo; Schneider, Naira F. Z.; Ramos, Gabriela Silva; Kreis, Wolfgang; Andrade, Saulo F.; De Souza Filho, Jose Dias; Braga, Fernão Castro; Alves, Ricardo J.; De Padua, Rodrigo Maia; Simões, Cláudia M. O. (European Journal of Medicinal Chemistry, 2019)
In recent years, new therapeutic possibilities were proposed for cardiac glycosides traditionally used to treat heart diseases, such as anticancer and antiviral activities. In this sense, this work aimed to synthesize the readily accessible 3β-azido-3-deoxydigitoxigenin (5) from digitoxigenin (1). Two new series of compounds were obtained from derivative (5): (i) O-glycosyl trizols through click chemistry with propargyl glycosides; and (ii) compounds substituted in the alpha carbonyl position with different residues linked via an amino-group. All obtained derivatives have their chemical structures confirmed, and their anti-herpes (against HSV-types 1 and 2 replication) and cytotoxic (against PC3, A549, HCT-8 and LNCaP cell lines) activities evaluated. Compounds 10 and 11 exhibited the most promising results against HSV-1 (KOS and 29-R strains) and HSV-2 (333 strain) replication with SI values > 1000. Both compounds were also the most cytotoxic for the human cancer cell lines tested with IC50 values similar to those of paclitaxel. They also presented reduced toxicity toward non-cancerous cell lines (MRC-5 and HGF cells). Promising compounds were tested in regard to their ability to inhibit Na+/K+-ATPase. The inhibition rate correlates suitably with the bioactivity demonstrated by those both compounds against the different human cancer cells tested as well as against HSV replication. Moreover, the results showed that specific chemical features of compound 10 and 11 influenced the bioactivities tested. In summary, it was possible to obtain novel digitoxigenin-derivatives with remarkable cytotoxic and anti-herpes activities as well as low toxicity and high selectivity. In this way, they could be considered potential molecules for the development of new drugs.
Keywords: Cardenolides; Digitoxigenin-derivatives; Anti-herpes; Cytotoxic

Prinzipien des Sekundärstoffwechsels. - Kreis, Wolfgang (Pharmakognosie - Phytopharmazie, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dbio.LPB.prinzi

Prinzipien des Sekundärstoffwechsels - Kreis, Wolfgang (Pharmakognosie - Phytopharmazie, 2010)

PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1,4-enone reductases): Catalytic and substrate promiscuity allows for realization of multiple pathways in plant metabolism. - Schmidt, Karin; Petersen, Jan; Munkert, Jennifer; Egerer-Sieber, Claudia; Hornig, Michael; Muller, Yves; Kreis, Wolfgang (Phytochemistry, 2018)
PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1,4-enone reductases) are involved in cardenolide and iridoid biosynthesis. We here investigated a PRISE (rAtSt5βR) from Arabidopsis thaliana, a plant producing neither cardenolides nor iridoids. The structure of rAtSt5βR was elucidated with X-ray crystallography and compared to the known structures of PRISEs from Catharanthus roseus (rCrISY) and Digitalis lanata (rDlP5βR). The three enzymes show a high degree of sequence and structure conservation in the active site. Amino acids previously considered to allow discrimination between progesterone 5β-reductase and iridoid synthase were interchanged among rAtSt5βR, rCrISY and rDlP5βR applying site-directed mutagenesis. Structural homologous substitutions had different effects, and changes in progesterone 5β-reductase and iridoid synthase activity were not correlated in all cases. Our results help to explain fortuitous emergence of metabolic pathways and product accumulation. The fact that PRISEs are found ubiquitously in spermatophytes insinuates that PRISEs might have a more general function in plant metabolism such as, for example, the detoxification of reactive carbonyl species.

Production of cardenolides by Digitalis cell cultures - models and process option - Kreis, Wolfgang; Fulzele, Devanand P.; Hoelz, Hubert; Val, John; Reinhard, Ernst (Plant Tissue Culture and Gene Manipulation for Breeding and Formation of Phytochemicals, 1992)
UnivIS-Import:2015-04-20:Pub.1992.nat.dbio.LPB.produc_3

Production of Deacetyllanatoside C by Digitalis Lanata Cell Cultures - Kreis, Wolfgang; Reinhard, Ernst (Progress in plant cellular and molecular biology Proceedings of the VIIth International Congress on Plant Tissue and Cell Culture, Amsterdam, The Netherlands, 24–29 June 1990, 1990)
Digitalis lanata cell suspension cultures are not able to synthesize cardiac glycosides de novo but can be used to modify exogenous ones. Among the conversion reactions observed, the regio- and stereospecific 12β-hydroxylation of digitoxin derivatives to their respective digoxin derivatives is of special interest (1). In recent years, research carried out by Reinhard and co-workers focussed on a process in which β-methyldigitoxin was used as the substrate for 12β-hydroxylation. The product, β-methyldigoxin, appeared in the spent medium where levels of 500–700 mg dm−3 could be reached. A semi-continuous process for the production of β-methyldigoxin was devised and run successfully in a 300 dm3 airlift bioreactor (2).
UnivIS-Import:2015-04-20:Pub.1990.nat.dbio.LPB.produc

Production of Forskolin by Axenic Coleus forskohlii Roots Cultivated in Shake Flasks and 20-litre Glass Jar Bioreactors - Krombholz, Richard; Mersinger, Rainer; Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1992)
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.produc

Production of the Cytotoxic Cardenolide Glucoevatromonoside by Semisynthesis and Biotransformation of Evatromonoside by a Digitalis lanata Cell Culture. - Munkert, Jennifer; Santiago Franco, Marina; Nolte, Elke; Silva, Izabella Thais; Oliveira Castilho, Rachel; Ottoni, Flaviano Melo; Schneider, Naira F. Z.; Oliveira, Mônica C.; Taubert, Helge; Bauer, Walter; Andrade, Saulo F.; Alves, Ricardo J.; et al. (Planta medica, 2017)
Recent studies demonstrate that cardiac glycosides, known to inhibit Na(+)/K(+)-ATPase in humans, have increased susceptibility to cancer cells that can be used in tumor therapy. One of the most promising candidates identified so far is glucoevatromonoside, which can be isolated from the endangered species Digitalis mariana ssp. heywoodii. Due to its complex structure, glucoevatromonoside cannot be obtained economically by total chemical synthesis. Here we describe two methods for glucoevatromonoside production, both using evatromonoside obtained by chemical degradation of digitoxin as the precursor. 1) Catalyst-controlled, regioselective glycosylation of evatromonoside to glucoevatromonoside using 2,3,4,6-tetra-O-acetyl-α-D-glucopyranosyl bromide as the sugar donor and 2-aminoethyldiphenylborinate as the catalyst resulted in an overall 30 % yield. 2) Biotransformation of evatromonoside using Digitalis lanata plant cell suspension cultures was less efficient and resulted only in an overall 18 % pure product. Structural proof of products has been provided by extensive NMR data. Glucoevatromonoside and its non-natural 1-3 linked isomer neo-glucoevatromonoside obtained by semisynthesis were evaluated against renal cell carcinoma and prostate cancer cell lines.

Progesterone 5β-reductase genes of the Brassicaceae family as function-associated molecular markers - Munkert, Jennifer; Costa, Catarina; Budeanu, Oleg; Petersen, Jan; Bertolucci, S; Fischer, Gabriele; Müller-Uri, Frieder; Kreis, Wolfgang (Plant Biology, 2015)

Progesterone 5β-reductase of Erysimum crepidifolium: cDNA cloning, expression in Escherichia coli, and reduction of enones with the recombinant protein - Bauer, Peter; Müller-Uri, Frieder; Kreis, Wolfgang; Burda, Edyta; Munkert, Jennifer (Phytochemistry, 2011)
UnivIS-Import:2015-03-09:Pub.2011.nat.dbio.LPB.proges

Progesterone 5β-reductases/iridoid synthases (PRISE): gatekeeper role of highly conserved phenylalanines in substrate preference and trapping is supported by molecular dynamics simulations - Petersen, Jan; Lanig, Harald; Munkert, Jennifer; Bauer, Peter; Müller-Uri, Frieder; Kreis, Wolfgang (Journal of Biomolecular Structure & Dynamics, 2015)

Purification and Characterization of a Cynaroside 7-O-beta-D-Glucosidase from Cynarae scolymi folium. - Nüßlein, Birgit; Kreis, Wolfgang (ISHS Acta Horticulture 681, 2005)
The enzymatic degradation of cynaroside (luteolin 7-O-glucoside) has been investigated in fresh and dried artichoke (Cynara scolymus L.) leaves. Plant and drug samples obtained from various sources differed considerably with regard to their ability to hydrolyse cynaroside during fermentation, and exogenous cynaroside when added to cell-free protein extracts. Extractable cynaroside 7-O-glucosidase was particularly high in artichoke leaves dried at 35° C. A β-glucosidase hydrolysing cynaroside was partially purified from the herbal drug Cynarae folium in 0.2 % yield by the combination of ammonium sulphate fractionation, hydrophobic interaction chromatography on Phenylsepharose 6FF, anion exchange chromatography on Source 30Q, gel filtration on Superdex 200 prep grade HR 16/60 and anion exchange chromatography on Resource Q. The molecular mass of the enzyme was about 160 kDa as determined by SDS PAGE. The role played by endogenous plant enzymes in stabilizing flavonoid glycosides during processing is discussed.
UnivIS-Import:2015-04-16:Pub.2005.nat.dbio.LPB.purifi
Keywords: Artichoke; Cynara scolymus; Herbal drug; Luteolin; Processing; Standardization

Purification and Characterization of a Flavone-7-O-Glucoside Specific Glucosidase from Ligulate Florets of Chamomilla recutita - Maier, Reinhard; Carle, Reinhold; Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1993)
Flavone content and glucosidase activity were analyzed in various species of the genera Chamomilla, Matricaria, and Anthemis, especially during the development of the chamomile flower heads. The accumulation profile of flavonoids and the increase in enzyme activity were similar during ontogenesis. The accumulation of apigenin derivatives in closely related species was always linked to the occurrence of a catabolic β-glucosidase in the respective plant organ. The flavone-glucoside-cleaving β-glucosidase (FGG) from the ligulate florets of chamomile was purified to electrophoretic homogeneity by the following procedure: ammonium sulphate fractionation, anion exchange on Mono Q, hydrophobic interaction chromatography on Bio-Gel TSK Phenyl-5-PW, and gel filtration on Superose 12. The M(r) of the native enzyme was determined by gel filtration (500 kDa) and native PAGE (334 kDa). Only one subunit with an M(r) of 60 kDa could be detected after SDS-PAGE. The isoelectric point as determined by chromatofocussing on Mono P was at pH 4.6. During the purification procedure only one glucosidase activity appeared. A partially purified enzyme was used for characterization. The temperature optimum was at 37°C and the pH-optimum 5.6. Energy of activation was 32.9 kJ/mol. The determination of the kinetic constants with various aryl glycosides proved a high affinity of the FGG towards flavone 7-O-glucosides. α-Glycosides and disaccharides were not hydrolyzed. Transglucosylation to an acceptor other than water was observed. Reagents interacting with sulfhydryl-groups strongly inhibited the enzyme.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.purifi
Keywords: chamomile flower heads; Chamomilla recutita; flavone 7-O-glucosides; glucosidase

Purification and characterization of a flavonol 3-O-beta-heterodisaccharidase from the dried herb of Fagopyrum esculentum Moench. - Baumgertel, Andreas; Grimm, Rudi; Eisenbeiß, Wilhelm Friedrich; Kreis, Wolfgang (Phytochemistry, 2003)
A flavonol-3-O-β-heterodisaccharide glycosidase (FHG I) was isolated from dried aerial tissues of Fagopyrum esculentum Moench (Fagopyri herba). It has a specific enzyme activity of ca. 3.5 nkat mg-1 protein in buffered extracts when rutin (quercetin-3-O-rutinoside) was used as substrate and an optimal enzyme activity was seen at around pH 4.8 and 30 °C. FHG I was purified about 156-fold to apparent homogeneity by hydrophobic interaction, anion exchange and size exclusion chromatographic steps. The apparent molecular mass of FHG I was 74.5 ± 2 kDa as determined by SDS-PAGE and it is a monomeric glycoprotein with a carbohydrate content of 23%. The isoelectric point as determined by isoelectric focusing was 5.7 and the energy of activation was 32 kJ mol-1. FHG I exhibits a high substrate specificity, preferring flavonol 3-O-glycosides comprising the disaccharide rutinose. The Km and Vmax values for the natural substrate rutin were calculated to be 0.561 μM and 745 nkat mg -1 protein, respectively. Two oligopeptide fragments obtained after enzymatic digestion of FHG I were sequenced and showed similarities to sequences of β-glucohydrolases from other plant species. Polyclonal antibodies were raised and their specificities determined. Another flavonol 3-O-β -heterodisaccharide glycosidase (FHG II) could also be detected in buckwheat herb, having a molecular mass of 85.3 ± 2 kDa and an isoelectric point between pH 6.0 and 6.5. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dbio.LPB.purifi
Keywords: β-Glycosidase; Fagopyrum esculentum; Polygonaceae; Purification; Rutin; Rutinoside

Purification and characterization of malonyl-coenzyme A: 21-hydroxypregnane 21-O-malonyltransferase (Dp21MaT) from leaves of Digitalis purpurea L. - Kuate, Serge Philibert; Maia de Pádua, Rodrigo; Eisenbeiß, Wilhelm Friedrich; Kreis, Wolfgang (Phytochemistry, 2008)
With respect to the cardenolide pathway and the characterization of enzymes involved in the formation of cardenolides, a malonyltransferase, termed malonyl-coenzyme A: 21-hydroxypregnane 21-O-malonyltransferase (Dp21MaT) has been purified. The enzyme catalyses the transfer of the malonyl moiety from malonyl-coenzyme A to 21-hydroxypregnane substrates. Malonyltransferase activity was checked in several potential starting materials including fresh leaves and cell suspension cultures from different plants. Fresh Digitalis purpurea L. leaves turned out to be the best enzyme source. The purification protocol included ammonium sulphate precipitation, hydrophobic interaction chromatography on Phenylsepharose 6 FF, ion exchange chromatography on Source 30 Q, affinity chromatography on Cibacron Blue 3GA and gel filtration on Superdex 75. Gel filtration and native SDS-PAGE analysis showed that Dp21MaT exists as a monomer with a molecular mass of 27 kDa. Its pI, as determined by isoelectric focusing, was 4.66. The enzyme showed maximal activity at pH 6.5 when incubated at 42 °C. The energy of activation was 29.28 kJ mol-1, whereas that of inactivation was 48.57 kJ mol-1. Dp21MaT was purified 252-fold with a yield of about 1%. Hanes plots of kinetic data indicated Km values of 99 μM (Vmax 47.57 μkat kg-1) and 28.44 μM (Vmax 39.4 μkat kg-1 protein) for 3β-benzoyloxy-5β-pregnane-14β,21-dihydroxy-20-one and malonyl-CoA, respectively. © 2007 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.purifi
Keywords: 21-Hydroxypregnane 21-O-malonyltransferase; 21-O-Hydroxypregnanes; Cardenolides; Cardiac glycosides; Digitalis purpurea; Enzyme purification; Malonyl-coenzyme A; Plantaginaceae

Purification and characterization of the cardenolide-specific β-glucohydrolase CGH I from Digitalis lanata leaves - May, Ursula; Kreis, Wolfgang (Plant Physiology and Biochemistry, 1997)
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.purifi

Purification and characterization of the cardenolide-specific β-glucohydrolase CGH II from Digitalis lanata leaves - Hornberger, Martin; Böttigheimer, Ute; Hillier-Kaiser, Andrea; Kreis, Wolfgang (Plant Physiology and Biochemistry, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.purifi_1

Purification of Δ(5)-3-ketosteroid isomerase from Digitalis lanata - Meitinger, Nadine; Geiger, Daniel; Augusto, Thierry W; Maia de Pádua, Rodrigo; Kreis, Wolfgang (Phytochemistry, 2014)

Rapid isolation of vacuoles from suspension-cultured Digitalis lanata cells - Kreis, Wolfgang; Reinhard, Ernst (Journal of Plant Physiology, 1985)

Recent Advances in Cardenolide Research. - Müller-Uri, Frieder; Kreis, Wolfgang (Buletinul Academiei de Stiinte a Moldovei, 2010)
UnivIS-Import:2015-03-09:Pub.2010.nat.dbio.LPB.recent

Recombinant Δ4,5-steroid 5β-reductases as biocatalysts for the reduction of activated C=C-double bonds in acyclic and monocyclic molecules - Burda, Edyta; Kraußer, Marina; Fischer, Gabriele; Hummel, Werner; Müller-Uri, Frieder; Kreis, Wolfgang; Gröger, Harald (dvanced Synthesis & Catalysis, 2009)
UnivIS-Import:2015-04-14:Pub.2009.nat.dbio.LPB.recomb

Regeneration and characterization of protoplast-derived cell lines from Digitalis lanata Ehrh. and Digitalis purpurea L. suspension cultures after electrofusion under microgravity conditions - Baumann, T; Kreis, Wolfgang; Mehrle, W; Hampp, R; Reinhard, Ernst (Proceedings of the 4th European symposium on life sciences research in space, 1990)
UnivIS-Import:2015-04-16:Pub.1990.nat.dbio.LPB.regene

Reinhard Pharmazeutische Biologie 1, Grundlagen für Studium und Praxis - Dingermann, Theodor; Kreis, Wolfgang; Rimpler, Horst; Zündorf, Ilse (Wissenschaftliche Verlagsgesellschaft mbH, 2009)

Reinhard Pharmazeutische Biologie, Grundlagen und Humanbiologie - Dingermann, Theodor; Kreis, Wolfgang; Nieber, Karen; Rimpler, Horst; Zündorf, Ilse (Wissenschaftliche Verlagsgesellschaft, 2016)

Reinigung einer Cynarosid-7-O-ß-D-glucosidase aus der Arzneidroge Cynarae folium (Artischockenblätter) - Nüßlein, Birgit; Kreis, Wolfgang (Journal of Applied Botany and Food Quality-Angewandte Botanik, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.reinig

Reinigung und Charakterisierung einer Polyphenoloxidase aus der Arzneidroge Echinaceae purpureae herba (Sonnenhutkraut) - Kreis, Wolfgang; Sußner, Ursula; Nüßlein, Birgit (Journal of Applied Botany and Food Quality-Angewandte Botanik, 2000)
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.reinig_97

Restoring cardenolide accumulation in RNAi-mediated DlP5 beta R1 and DlP5 beta R2 knockdown shoot culture lines of Digitalis lanata and studying the effects of precursor feeding on cardenolide free dark-cultured D. lanata shoots - Ignatova, Anastasiia; Klein, J.; Leykauf, Tim; Kreis, Wolfgang; Munkert, Jennifer (PLANTA MEDICA, 2021)
CRIS-Team WoS Importer:2021-12-31

RNAi-mediated gene knockdown of progesterone 5β-reductases in Digitalis lanata reduces 5β-cardenolide content - Klein, Jan; Horn, Elisa; Ernst, Mona; Leykauf, Tim; Leupold, Tamara; Dorfner, Maja; Wolf, Laura-Sophie; Ignatova, Anastasiia; Kreis, Wolfgang; Munkert, Jennifer (Plant Cell Reports, 2021)
Key message: Studying RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of Digitalis lanata, we here provide direct evidence for the participation of PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) in 5β-cardenolide formation. Abstract: Progesterone 5β-reductases (P5βR) are assumed to catalyze the reduction of progesterone to 5β-pregnane-3,20-dione, which is a crucial step in the biosynthesis of the 5β-cardenolides. P5βRs are encoded by VEP1-like genes occurring ubiquitously in embryophytes. P5βRs are substrate-promiscuous enone-1,4-reductases recently termed PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes). Two PRISE genes, termed DlP5βR1 (AY585867.1) and DlP5βR2 (HM210089.1) were isolated from Digitalis lanata. To give experimental evidence for the participation of PRISEs in 5β-cardenolide formation, we here established several RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of D. lanata. Cardenolide contents were lower in D. lanata P5βR-RNAi lines than in wild-type shoots. We considered that the gene knockdowns may have had pleiotropic effects such as an increase in glutathione (GSH) which is known to inhibit cardenolide formation. GSH levels and expression of glutathione reductase (GR) were measured. Both were higher in the Dl P5βR-RNAi lines than in the wild-type shoots. Cardenolide biosynthesis was restored by buthionine sulfoximine (BSO) treatment in Dl P5βR2-RNAi lines but not in Dl P5βR1-RNAi lines. Since progesterone is a precursor of cardenolides but can also act as a reactive electrophile species (RES), we here discriminated between these by comparing the effects of progesterone and methyl vinyl ketone, a small RES but not a precursor of cardenolides. To the best of our knowledge, we here demonstrated for the first time that P5βR1 is involved in cardenolide formation. We also provide further evidence that PRISEs are also important for plants dealing with stress by detoxifying reactive electrophile species (RES).
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cardenolide biosynthesis; Digitalis lanata; Glutathione; Progesterone 5β-reductases (P5βR); Reactive electrophile species; RNAi-mediated knockdown

RNAi mediated knock down of 3 beta-hydroxysteroid dehydrogenases in Digitalis lanata shoot cultures - Leykauf, Tim; Klein, Jan; Ernst, Mathias; Kreis, Wolfgang; Munkert, Jennifer (PLANTA MEDICA, 2019)
CRIS-Team WoS Importer:2020-01-10

Sekundäre Pflanzenstoffe und Krebs. - Kreis, Wolfgang (Deutsche Zeitschrift für Onkologie, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dbio.LPB.sekund

Selective Uptake and Vacuolar Storage of Primary Cardiac Glycosides by Suspension-cultured Digitalis lanata Cells - Kreis, Wolfgang; Reinhard, Ernst (Journal of Plant Physiology, 1987)
UnivIS-Import:2015-03-05:Pub.1987.nat.dbio.LPB.select

Semicontinuous Cultivation of Digitalis lanata Cells. Production of beta-Methyldigoxin in a 300-L Airlift Bioreactor. - Kreis, Wolfgang; Reinhard, Ernst; Barthlen, U; Helmbold, U (Biotechnology and Bioengineering, 1989)
UnivIS-Import:2015-03-05:Pub.1989.nat.dbio.LPB.semico

Semisynthetic Cardenolides Acting as Antiviral Inhibitors of Influenza A Virus Replication by Preventing Polymerase Complex Formation - Boff, Laurita; Schreiber, André; Matos, Aline da Rocha; Del Sarto, Juliana L; Brunotte, Linda; Munkert, Jennifer; Ottoni, Flaviano Melo; Ramos, Gabriela Silva; Kreis, Wolfgang; Braga, Fernão Castro; Alves, Ricardo José; Maia de Pádua, Rodrigo; et al. (Molecules, 2020)

Separation of cardiac glycosides by micellary electrokinetic capillary electrophoresis. - Gaus, Hans-Joachim; Treumann, Hans-Joachim; Kreis, Wolfgang; Bayer, Ernst (Journal of Chromatography A, 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.separa

Shoot-tip Cultivation and Cardenolide Content Analysis of Natural Populations of Digitalis lanata Ehrh. subsp. lanata (wooly foxglove) in Thrace Region - Yücesan, Buhara; Eker, İsmail and Lazzarini, Luiz Eduardo Santos and Aslam, Noreen and Mohammed, Aliyu and Pinto, Jose Eduardo Brasil Pereira and Kreis, Wolfgang and Gürel, Ekrem (International Journal of Agriculture and Wildlife Science, 2018)
Digitalis lanata, due to the presence of cardenolides in the leaves, is widely used in drug industry for the treatments of congestive heart diesases. In this present study, natural populations of D. lanata in Thrace region were collected. Thereafter, cardiac glycoside analysis of D. lanata subsp. lanata grown in natural habitats and micropropagation from shoot tips were established as a model work for a consistent and a sustainable plant production. Of the cardenolides, Lan A (ranging between 24.8 and 300.4 mg 100g-1) and Lan C (42.1 and 258 mg 100 g-1 were predominantly found in the samples as compared to lanatoside B, digoxin and digitoxin. After seed germination, shoot-tip cultivation was achieved after a subsequent shoot and root formation on MS medium. Indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) depending on their concentrations were found to be effective in shoot and root formation accordingly. Maximum two shoots from shoot tips were produced after 8 weeks of cultivation, and at the end of 12th weeks of cultivation each shoots produced an average number of 6.4 roots in 8.1 cm length. Acclimatization was also achieved successfully with a maximum survival rate (95 %) for 4 weeks. This study is the first report on cardenolide profiling of Thracian D. lanata at different locations, and shoot tip cultivation of the population selected under in vitro condition
Keywords: Digitalis lanata; Wooly foxglove; Clonal propagation; Cardenolides; Thrace

Somaclonal variation of cardenolide content in Heywood's foxglove, a source for the antiviral cardenolide glucoevatromonoside, regenerated from permanent shoot culture and callus - Kreis, Wolfgang; Haug, Birgit; Yücesan, Buhara (In Vitro Cellular & Developmental Biology-Plant, 2014)

Spontaneous butenolide ring formation of pregnane-21-O-malonyl hemiesters under mild reaction conditions is facilitated by the 14β-hydroxy group present in all natural cardenolides - Maia de Pádua, Rodrigo; Meitinger, Nadine; Hennemann, Matthias; Schebitz, Pia; Waibel, Reiner; Löber, Stefan; Gmeiner, Peter; Clark, Timothy; Kreis, Wolfgang (Tetrahedron, 2016)

Storage of cardenolides in Digitalis lanata cells. Effect of dimethyl sulfoxide (DMSO) on cardenolide uptake and release - Kreis, Wolfgang; Hoelz, Hubert; May, Ursula; Reinhard, Ernst (Plant Cell Tissue and Organ Culture, 1990)
Varius Digitalis lanata suspension cultures differing in their potential for biotransforming cardenolides were used to investigate the influence of dimethyl sulfoxide (DMSO) on cardenolide uptake, biotransformation and release. DMSO inhibited the accumulation of secondary glycosides (e.g. lanatoside A) but not of primary glycosides (e.g. β-methyldigitoxin). Cardenolide transformation was affected by DMSO both in vivo and in vitro resulting in almost complete inhibition at 20% DMSO (biotransformations in vivo) or 30 to 40% (enzyme activities in vitro). Further evidence has been obtained that cellular cardenolide accumulation during biotransformation of digitoxin involves the diffusion of secondary glycosides across the plasmalemma and the active uptake and vacuolar storage of primary glycosides. DMSO was used to permeabilize cultured Digitalis lanata cells. Only DMSO concentrations higher than 11% caused any release of cardenolides. The cells were, however, irreversibly damaged by this treatment. © 1990 Kluwer Academic Publishers.
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.storag
Keywords: cardiac glycosides; Digitalis lanata; dimethyl sulfoxide (DMSO); plant cell culture; storage; uptake

Storage of cardiac glycosides in vacuoles of Digitalis lanata mesophyll cells - Hoelz, Hubert; Kreis, Wolfgang; Haug, Birgit; Reinhard, Ernst (Phytochemistry, 1992)
The intracellular distribution of cardenolides in mesophyll cells of Digitalis lanata was investigated. Plantlets were grown under axenic conditions. Protoplasts were isolated from sliced leaves and lysed to yield intact vacuoles which were subsequently purified by flotation centrifugation. The cardenolide contents of mesophyll cells, protoplasts and vacuoles were analysed by HPLC. Primary glycosides, e.g. the lanatosides A and C, were found to be stored exclusively in the vacuoles. Although present in quite high amounts in leaf tissue, secondary glycosides, such as α-acetyldigoxin or α-acetyldigitoxin, could not be detected in vacuoles isolated from mesophyll cells. It is concluded that in Digitalis leaves cardenolides are stored solely as primary glycosides, whereas secondary glycosides found in leaf extracts are either biosynthetic intermediates or degradation products. © 1992.
UnivIS-Import:2015-03-05:Pub.1992.nat.dbio.LPB.storag
Keywords: cardiac glycosides; compartmentalization; Digitalis lanata; protoplasts; Scrophulariaceae; vacuoles

Structure-specificity relationship of cardiac glycosides as a substrate for glucohydrolase II - Terada, Yukimasa; Misoi, Rumi; Watanabe, Naoharu; Hornberger, Martin; Kreis, Wolfgang (Chemical & Pharmaceutical Bulletin, 2000)
Cardenolide glucohydrolase II (CGH II) is a cardenolide-specific glucohydrolase obtained from Digitalis lanata leaves. We investigated the structure-specificity relationship of several cardenolide disaccharides as a substrate for CGH II. Conformation analysis of the substrates was performed using molecular mechanics calculations. The sugar chain conformation of two inert glycosides was significantly different from that of the other glycosides. The other two glycosides, which were weak substrates of CGH II, were suggested to have an intramolecular hydrogen bond between the sugar groups. It was deduced that this hydrogen bond restricts the conformational change of the sugar chain and prevents the glycosides from enzymatic recognition.
UnivIS-Import:2015-03-06:Pub.2000.nat.dbio.LPB.struct
Keywords: Cardenolide glucohydrolase II (CGH II); Cardiac glycoside; Conformation analysis; Molecular mechanics; Structure- specificity relationship

Subcellular Localization of Primary and Secondary Cardiac Glycosides and the Related 16' -O-Glucosyltransferase in Cell Suspension Cultures of Digitalis lanata - Kreis, Wolfgang; May, Ursula; Reinhard, Ernst (Plant Vacuoles. Their importance for plant cell compartmentation and their application in biotechnology, 1987)
UnivIS-Import:2015-04-17:Pub.1987.nat.dbio.LPB.subcel

Synthesis of a putative substrate for malonyl-coenzyme A: 21-hydroxypregnane 21-O-malonyltransferase and develoopment of an HPLC method for the quantification of the enzyme reaction. - Kuate, Serge Philibert; Maia de Pádua, Rodrigo; Poumale, Hervé Martial P; Kreis, Wolfgang (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dbio.LPB.synthe

Synthesis of cardenolide glycosides and putative biosynthesis precursors of cardenolide glycosides - Luta, Melitta; Hensel, Andreas; Kreis, Wolfgang (Steroids, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dbio.LPB.synthe

Synthesis of Uridine 5`-(alpha-D-Fucopyranosyl Diphosphate) and (Digitoxigenin-3beta-yl)-beta-D-fucopyranoside and Enzymatic beta-D-Fucosylation of Cardenolide Aglycones in Digitalis lanata. - Faust, Thomas; Theurer, Christoph; Eger, Kurt; Kreis, Wolfgang (Bioorganic Chemistry, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dbio.LPB.synthe

The catalytic mechanism of the 3-ketosteroid isomerase of Digitalis lanata involves an intramolecular proton transfer and the activity is not associated with the 3 beta-hydroxysteroid dehydrogenase activity - Meitinger, Nadine; Munkert, Jennifer; Maia de Pádua, Rodrigo; De Souza Filho, Jose Dias; Maid, Harald; Bauer, Walter; Braga, Fernao Castro; Kreis, Wolfgang (Tetrahedron Letters, 2016)
Studies indicate that the isomerization catalyzed by the Dl3KSI proceeds without significant isotope exchange between the medium and the steroid and thus involves an intramolecular proton transfer consistent with the mechanism of the bacterial 3-ketosteroid isomerase of Pseudomonas testosteroni. For the rDl3 beta HSD as well as under non-enzymatic conditions deuterium was incorporated from the incubation buffer during isomerization. Together with a comparison of the rate of isomerization under the different conditions, it was demonstrated that rDl3 beta HSD does not possess 3-ketosteroid isomerase activity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cardenolide biosynthesis; Digitalis lanata; 3 beta-Hydroxysteroid dehydrogenase; 3-Ketosteroid isomerase; Isoprogesterone; Progesterone

The crystal structure of progesterone 5beta-reductase from Digitalis lanata defines a novel class of short-chain dehydrogenases/reductases - Thorn, Andrea; Egerer-Sieber, Claudia; Jäger, Christof; Herl, Vanessa; Müller-Uri, Frieder; Kreis, Wolfgang; Muller, Yves (Journal of Biological Chemistry, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.thecry

The Foxgloves (Digitalis) Revisited - Kreis, Wolfgang (Planta Medica, 2017)

The new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) efficiently suppresses cell growth in human leukemia and urologic tumor cell lines - Nolte, Elke; Sobel, Anna; Wach, Sven; Hertlein, Heidi; Ebert, Nadja; Müller-Uri, Frieder; Slany, Robert; Taubert, Helge; Wullich, Bernd; Kreis, Wolfgang (Anticancer Research, 2015)
Background/Aim: The use of cardenolides in the treatment of cardiac insufficiency is well-established. However, the potential of cardenolides in tumor therapy has not been comprehensively studied. The aim of the present study was to characterize the cytotoxic effects of the new semisynthetic cardenolide analog AMANTADIG (3β-[2-(1-amantadine)-1- on-ethylamine]-digitoxigenin), and the cardenolide digitoxin on leukemia and urological tumor cell lines. Materials and Methods: The anti-proliferative effects of AMANTADIG and digitoxin on leukemia and urological cancer cell lines were analyzed using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction viability assay. Results: AMANTADIG and digitoxin exhibited antiproliferative activities against the leukemia cell lines in the low nanomolar range. The prostate cancer and renal cell carcinoma cell lines were equally sensitive to AMANTADIG and digitoxin, however, the leukemia cell lines were more sensitive to both cardenolides. Conclusion: The new cardenolide analog AMANTADIG appears effective in cell growth inhibition of leukemia and urological tumor cell lines.
Keywords: 3β-[2-(1-Amantadine)-1-on-ethylamine]-digitoxigenin; AMANTADIG; Cardenolide analog; Human leukemia cells; Human urological cancer cells; Porcine cerebral cortex Na+/K+-ATPase

The plant cell wall - a potential source for pharmacologically active polysaccharides - Hensel, Andreas; Schmidgall, Jörg; Kreis, Wolfgang (Pharmaceutica Acta Helvetiae, 1998)
Four main crude polysaccharide fractions, which represented the complete polymeric carbohydrate pool, were isolated by sequential extraction from Digitalis purpurea leaves. These crude fractions were fractionated further by ion exchange and gel permeation chromatography in order to obtain homogenous polysaccharide fractions. The following polymers were identified: the water soluble reserve polysaccharides were mainly composed of neutral and acidic arabinogalactans, neutral and acidic glucomannans and starch. Pectic material from a sodium carbonate extract was identified as rhamnogalacturonan. Hemicellulosic cell wall polysaccharides consisted of a neutral, tow substituted arabinoxyloglucan and several acidic xylans. Hemicellulosic polymers associated with cellulose were shown to be highly branched xyloglucans. Extracellular polysaccharides from Digitalis lanata suspension-cultured cells were fractionated and arabinoxyloglucans, as well as neutral and acidic arabinogalactans were identified. 2,6-Dideoxy sugars, the typical constituents of cardiac glycosides in Digitalis, are not part of the polysaccharide pool of both systems investigated.
UnivIS-Import:2015-03-05:Pub.1998.nat.dbio.LPB.thepla
Keywords: 2; 6-Dideoxy sugars; Arabinogalactan; Cell culture; Digitalis lanata; Digitalis purpurea; Glucomannan; Polysaccharides; Scrophulariaceae; Xylan; Xyloglucan

The Production of Secondary Metabolites by 'Plant Cells Cultivated in Bioreactors. - Kreis, Wolfgang; Reinhard, Ernst (Planta Medica, 1989)
UnivIS-Import:2015-03-05:Pub.1989.nat.dbio.LPB.thepro

The VEP1 gene (At4g24220) encodes a short-chain dehydrogenase/reductase with 3-oxo-Δ4,5-steroid 5β-reductase activity in Arabidopsis thaliana L. - Herl, Vanessa; Fischer, Gabriele; Reva, Veaceslav A.; Stiebritz, Martin; Muller, Yves; Müller-Uri, Frieder; Kreis, Wolfgang (Biochimie, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dbio.LPB.thevep

Three-step test system for the identification of novel GABAa receptor modulating food plants - Sahin, Sümeyye; Eulenburg, Volker; Kreis, Wolfgang; Villmann, Carmen; Pischetsrieder, Monika (Plant Foods For Human Nutrition, 2016)
Potentiation of γ-amino butyric acid (GABA)-induced GABAA receptor (GABAAR) activation is a common pathway to achieve sedative, sleep-enhancing, anxiolytic, and antidepressant effects. Presently, a three-component test system was established for the identification of novel GABAAR modulating food plants. In the first step, potentiation of GABA-induced response of the GABAAR was analysed by two-electrode voltage clamp (TEVC) for activity on human α1β2-GABAAR expressed in Xenopus laevis oocytes. Positively tested food plants were then subjected to quantification of GABA content by high-performance liquid chromatography with fluorescence detection (HPLC–FLD) to exclude test foods, which evoke a TEVC-response by endogenous GABA. In the third step, specificity of GABAA-modulating activity was assessed by TEVC analysis of Xenopus laevis oocytes expressing the homologous glycine receptor (GlyR). The three-component test was then applied to screen 10 aqueous extracts of food plants for their GABAAR activity. Thus, hop cones (Humulus lupulus) and Sideritis sipylea were identified as the most potent specific GABAAR modulators eliciting significant potentiation of the current by 182 ± 27 and 172 ± 19 %, respectively, at the lowest concentration of 0.5 μg/mL. The extracts can now be further evaluated by in vivo studies and by structural evaluation of the active components.
EVALuna2:4740
Keywords: GABAA receptor; GABA; Glycine receptor; Sideritis; Lemon balm leaves; Hop cones

Truncation of N-terminal regions of Digitalis lanata progesterone 5β-reductase alters catalytic efficiency and substrate preference - Rudolph, Kristin; Bauer, Peter; Schmid, Benedikt; Müller-Uri, Frieder; Kreis, Wolfgang (Biochimie, 2014)

Two-stage cultivation of Digitalis lanata cells: Semicontinuous production of deacetyllanatoside C in 20-litre airlift bioreactors. - Kreis, Wolfgang; Reinhard, Ernst (Journal of Biotechnology, 1990)
A two-stage cultivation method was employed to develop a semicontinuous biotransformation process for the production of deacetyllanatoside C, a cardenolide of the important digoxin series. Digitoxin was used as the substrate for biotransformation. The process was optimized in 1-l shake flasks and then established on the 20-l scale using two airlift bioreactors, one for cell growth (working volume 12 litres) and another for deacetyllanatoside C production (working volume 18 litres). Growth and production phases were synchronized and the process finally ran semicontinuously in 7-d cycles. Six consecutive production runs were performed yielding a total of 43.8 g deacetyllanatoside C. © 1990.
UnivIS-Import:2015-03-05:Pub.1990.nat.dbio.LPB.twosta
Keywords: 12β-Hydroxylation; Biotransformation; Digitalis lanata; Plant cell culture; Semi-continuous process

UDP-glucose:digitoxin 16'-O-glucosyltransferase from suspension-cultured Digitalis lanata cells - Kreis, Wolfgang; May, Ursula; Reinhard, Ernst (Plant Cell Reports, 1986)

Uptake, Transport and Storage of Cardenolides in Foxglove, Cardenolide Sinks and Occurence of Cardenolides in the Sieve Tubes of Digitalis lanata - Christmann, J; Kreis, Wolfgang; Reinhard, Ernst (Botanica Acta : Berichte der Deutschen Botanischen Gesellschaft, 1993)
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.uptake

Using progesterone 5beta-reductase, a gene encoding a key enzyme in the cardenolide biosynthesis, to infer the phylogeny of the genus Digitalis. - Herl, Vanessa; Albach, Dirk C.; Müller-Uri, Frieder; Bräuchler, Christian; Heubl, Günther; Kreis, Wolfgang (Plant Systematics and Evolution, 2007)
UnivIS-Import:2015-03-09:Pub.2008.nat.dbio.LPB.usingp

Variation of cardenolides with growth in a Digitalis lanata Brazilian cultivar - Braga, Fernão Castro; Kreis, Wolfgang; Récio, Rubens Almeida; De Oliveira, Alaíde Braga (Phytochemistry, 1997)
The content of the main cardenolides in Digitalis lanata harvested in Brazil was determined by HPLC, in two different stages of growth. The analysed plants, totaling 49, presented great variation in the contents of lanatoside C and digoxin (jointly quantified), lanatoside A, lanatoside B, glucoevatromonoside, odorobioside G, glucogitoroside, glucoverodoxine, glucodigifucoside and digitalinum verum. The sum of the analysed cardenolides in the 12-month-old plants was higher than the determined concentrations in plants collected later (18 months) (P < 0.0001). Lanatoside C and digoxin were the major cardenolides in both groups, followed by glucodigifucoside. Lanatoside A content decreased in the older plants (P < 0.0001), whereas lanatoside C showed an opposite trend (P < 0.05). The estimated average dry leaf content of lanatoside C and digoxin was 1820 ± 900 nmol g-1 in the younger plants, and 2040 ± 840 nmol g-1 in the older plants. Some individual plants have shown a leaf content above 3500 nmol g-1 of these cardenolides and will be selected for improvement of the cultivar.
UnivIS-Import:2015-03-05:Pub.1997.nat.dbio.LPB.variat
Keywords: Brazilian cultivar; cardenolides; cardenolides growth content variation; Digitalis lanata; Scrophulariaceae

Vein Patterning 1-encoded progesterone 5beta-reductase: Activity-guided improvement of catalytic efficiency - Bauer, Peter; Rudolph, Kristin; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2012)
UnivIS-Import:2015-03-09:Pub.2012.nat.dbio.LPB.veinpa

Zellulärer Transport und Speicherung von Naturstoffen. Die Bedeutung der Vakuole im pflanzlichen Sekundärstoffwechsel. - Kreis, Wolfgang; Hoelz, Hubert (Naturwissenschaftliche Rundschau, 1991)
UnivIS-Import:2015-03-05:Pub.1991.nat.dbio.LPB.zellul

Δ5-3β-hydroxysteroid dehydrogenase (3βHSD) from Digitalis lanata. Heterologous expression and characterisation of the recombinant enzyme - Herl, Vanessa; Frankenstein, Jördis; Meitinger, Nadine; Müller-Uri, Frieder; Kreis, Wolfgang (Planta Medica, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dbio.LPB.clonin